4U 1909+07: a well-hidden pearl - Fürst, Felix; Kreykenbohm, Ingo; Suchy, S.; Barragan, L.; Wilms, Jörn; Rothschild, R. E.; Pottschmidt, K. (Astronomy & Astrophysics, 2011)
We present the first detailed spectral and timing analysis of the high mass X-ray binary (HMXB) 4U1909+07 with INTEGRAL and RXTE. 4U1909+07 is detected in the ISGRI 20-40 keV energy band with an average countrate of 2.6 cts s(-1). The pulse period of similar to 604 s is not stable, but changing erratically on timescales of years. The pulse profile is strongly energy dependent: it shows a double peaked structure at low energies, the secondary pulse decreases rapidly with increasing energy and above 20 keV only the primary pulse is visible. This evolution is consistent between PCA, HEXTE, and ISGRI. The phase averaged spectrum can be well described by the sum of a photoabsorbed power law with a cutoff at high energies and a blackbody component. To investigate the pulse profile, we performed phase resolved spectral analysis. We find that the changing spectrum can be best described with a variation of the folding energy. We rule out a correlation between the black body component and the continuum variation and discuss possible accretion geometries.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

Accreting on the Edge: A Luminosity-dependent Cyclotron Line in the Be/X-Ray Binary 2S 1553-542 Accompanied by Accretion Regimes Transition - Malacaria, C.; Bhargava, Y.; Coley, Joel B.; Ducci, L.; Pradhan, P.; Ballhausen, R.; Fuerst, F.; Islam, N.; Jaisawal, G. K.; Jenke, P.; Kretschmar, P.; Kreykenbohm, Ingo; et al. (Astrophysical Journal, 2022)
Accreting X-ray pulsars undergo luminous X-ray outbursts during which the luminosity-dependent spectral and timing features of the neutron star's emission can be analyzed in detail, thus shedding light on the accretion regime at work. We took advantage of a monitoring campaign that was performed with NuSTAR, Swift/XRT, AstroSat and NICER to follow the Be/X-ray Binary 2S 1553-542 along one of its rare outbursts, and thus trace its spectral and timing evolution. We report the discovery of a luminosity-dependent cyclotron line energy for the first time in this source. The pulse profiles and pulsed fraction also show variability along the outburst, which is consistent with the interpretation that the source transitions from the subcritical to the supercritical accretion regime, separated by a critical luminosity of L (crit) approximate to 4 x 10(37) erg s(-1).
CRIS-Team WoS Importer:2022-04-01

A COMPREHENSIVE SPECTRAL ANALYSIS OF THE X-RAY PULSAR 4U 1907+09 FROM TWO OBSERVATIONS WITH THE SUZAKU X-RAY OBSERVATORY - Rivers, Elizabeth; Markowitz, Alex; Pottschmidt, Katja; Roth, Stefanie; Barragan, Laura; Fürst, Felix; Suchy, Slawomir; Kreykenbohm, Ingo; Wilms, Jörn; Rothschild, Richard (Astrophysical Journal, 2010)
We present results from two observations of the wind-accreting X-ray pulsar 4U 1907+09 using the Suzaku Observatory. The broadband time-averaged spectrum allows us to examine the continuum emission of the source and the cyclotron resonance scattering feature at similar to 19 keV. Additionally, using the narrow CCD response of Suzaku near 6 keV allows us to study in detail the Fe K bandpass and to quantify the Fe K beta line for this source for the first time. The source is absorbed by fully covering material along the line of sight with a column density of N-II similar to 2 x 10(22) cm(-2), consistent with a wind-accreting geometry, and a high Fe abundance (similar to 3-4 times solar). Time-and phase-resolved analyses allow us to study variations in the source spectrum. In particular, dips found in the 2006 observation which are consistent with earlier observations occur in the hard X-ray bandpass, implying a variation of the whole continuum rather than occultation by intervening material, while a dip near the end of the 2007 observation occurs mainly in the lower energies implying an increase in N-H along the line of sight, perhaps indicating clumpiness in the stellar wind.
Keywords: pulsars: individual (4U 1907+09); stars: magnetic field; X-rays: binaries; X-rays: stars

A DOUBLE-PEAKED OUTBURST OF A 0535+26 OBSERVED WITH INTEGRAL, RXTE, AND SUZAKU - Caballero, I.; Pottschmidt, K.; Marcu, D. M.; Barragan, L.; Ferrigno, C.; Klochkov, D.; Heras, J. A. Zurita; Suchy, S.; Wilms, Jörn; Kretschmar, Peter; Santangelo, A.; Kreykenbohm, Ingo; et al. (Astrophysical Journal Letters, 2013)
The Be/X-ray binary A 0535+26 showed a normal (type I) outburst in 2009 August. It is the fourth in a series of normal outbursts associated with the periastron, but is unusual because it presented a double-peaked light curve. The two peaks reached a flux of similar to 450 mCrab in the 15-50 keV range. We present results of the timing and spectral analysis of INTEGRAL, RXTE, and Suzaku observations of the outburst. The energy-dependent pulse profiles and their evolution during the outburst are studied. No significant differences with respect to other normal outbursts are observed. The centroid energy of the fundamental cyclotron line shows no significant variation during the outburst. A spectral hardening with increasing luminosity is observed. We conclude that the source is accreting in the sub-critical regime. We discuss possible explanations for the double-peaked outburst.
Keywords: pulsars: individual (A 0535+26); stars: magnetic field; X-rays: binaries; X-rays: stars

Advances in Understanding High-Mass X-ray Binaries with INTEGRALand Future Directions - Kretschmar, Peter; Furst, Felix; Sidoli, Lara; Bozzo, Enrico; Alfonso-Garzon, Julia; Bodaghee, Arash; Chaty, Sylvain; Chernyakova, Masha; Ferrigno, Carlo; Manousakis, Antonios; Negueruela, Ignacio; Postnov, Konstantin; et al. (New Astronomy Reviews, 2019)
High mass X-ray binaries are among the brightest X-ray sources in the Milky Way, as well as in nearby Galaxies. Thanks to their highly variable emissions and complex phenomenology, they have attracted the interest of the high energy astrophysical community since the dawn of X-ray Astronomy. In more recent years, they have challenged our comprehension of physical processes in many more energy bands, ranging from the infrared to very high energies. In this review, we provide a broad but concise summary of the physical processes dominating the emission from high mass X-ray binaries across virtually the whole electromagnetic spectrum. These comprise the interaction of stellar winds with the high gravitational and magnetic fields of compact objects, the behaviour of matter under extreme magnetic and gravity conditions, and the perturbation of the massive star evolutionary processes by presence in a binary system. We highlight the role of the INTEGRAL mission in the discovery of many of the most interesting objects in the high mass X-ray binary class and its contribution in reviving the interest for these sources over the past two decades. We show how the INTEGRAL discoveries have not only contributed to significantly increase the number of high mass X-ray binaries known, thus advancing our understanding of the population as a whole, but also have opened new windows of investigation that stimulated the multi-wavelength approach nowadays common in most astrophysical research fields. We conclude the review by providing an overview of future facilities being planned from the X-ray to the very high energy domain that will hopefully help us in finding an answer to the many questions left open after more than 18 years of INTEGRAL scientific observations.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; gamma rays: observations; INTEGRAL observatory; pulsars: general; stars: neutron; X-rays: binaries

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

An evaluation of the exposure in nadir observation of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Ambrosio, M.; Anchordoqui, L.; Anzalone, Anna; Arai, Y.; Aramo, Carla; Asano, K.; Ave, M.; Barrillon, P.; et al. (Astroparticle Physics, 2013)
We evaluate the exposure during nadir observations with JEM-EUSO, the Extreme Universe Space Observatory, on-board the Japanese Experiment Module of the International Space Station. Designed as a mission to explore the extreme energy Universe from space, JEM-EUSO will monitor the Earth's nighttime atmosphere to record the ultraviolet light from tracks generated by extensive air showers initiated by ultra-high energy cosmic rays. In the present work, we discuss the particularities of space-based observation and we compute the annual exposure in nadir observation. The results are based on studies of the expected trigger aperture and observational duty cycle, as well as, on the investigations of the effects of clouds and different types of background light. We show that the annual exposure is about one order of magnitude higher than those of the presently operating ground-based observatories. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ultra High Energy Cosmic Rays; Space-based experiment; Extensive air showers; JEM-EUSO mission

An overview of the JEM-EUSO program and results - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
The field of UHECRs (Ultra-High energy cosmic Rays) and the understanding of particle acceleration in the cosmos, as a key ingredient to the behaviour of the most powerful sources in the universe, is of outmost importance for astroparticle physics as well as for fundamental physics and will improve our general understanding of the universe. The current main goals are to identify sources of UHECRs and their composition. For this, increased statistics is required. A space-based detector for UHECR research has the advantage of a very large exposure and a uniform coverage of the celestial sphere. The aim of the JEM-EUSO program [1] is to bring the study of UHECRs to space. The principle of observation is based on the detection of UV light emitted by isotropic fluorescence of atmospheric nitrogen excited by the Extensive Air Showers (EAS) in the Earth's atmosphere and forward-beamed Cherenkov radiation reflected from the Earth's surface or dense cloud tops. In addition to the prime objective of UHECR studies, JEM-EUSO will do several secondary studies due to the instruments' unique capacity of detecting very weak UV-signals with extreme time-resolution around 1 μs: meteors, Transient Luminous Events (TLE), bioluminescence, maps of human generated UV-light, searches for Strange Quark Matter (SQM) and high-energy neutrinos, and more. The JEM-EUSO program includes several missions from ground (EUSO-TA [2]), from stratospheric balloons (EUSO-Balloon [3], EUSO-SPB1 [4], EUSO-SPB2 [5]), and from space (TUS [6], Mini-EUSO [7]) employing fluorescence detectors to demonstrate the UHECR observation from space and prepare the large size missions K-EUSO [8] and POEMMA [9]. A review of the current status of the program, the key results obtained so far by the different projects, and the perspectives for the near future are presented.
CRIS-Team Scopus Importer:2024-12-16

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A precessing Be disc as a possible model for occultation events in GX 304-1 - Kühnel, Matthias; Rothschild, R. E.; Okazaki, A. T.; Müller, Sebastian; Pottschmidt, K.; Ballhausen, Ralf; Choi, J.; Kreykenbohm, Ingo; Fuerst, F.; Marcu-Cheatham, D. M.; Hemphill, P.; Sagredo, Macarena; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the RXTE detection of a sudden increase in the absorption column density, N-H, during the 2011 May outburst of GX 304-1. The NH increased up to similar to 16 x 10(22) atoms cm(-2), which is a factor of 3-4 larger than what is usually measured during the outbursts of GX 304-1 as covered by RXTE. Additionally, an increase in the variability of the hardness ratio as calculated from the energy resolved RXTE-Proportional Counter Array light curves is measured during this time range. We interpret these facts as an occultation event of the neutron star by material in the line of sight. Using a simple 3D model of an inclined and precessing Be disc around the Be-type companion, we are able to qualitatively explain the NH evolution over time. We are able to constrain the Be disc density to be of the order of 10(-11) g cm(-3). Our model strengthens the idea of inclined Be discs as origin of double-peaked outbursts as the derived geometry allows accretion twice per orbit under certain conditions.
Keywords: occultations; stars: neutron; pulsars: individual: GX 304-1; X-rays: binaries

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

A study on UV emission from clouds with Mini-EUSO - Golzio, Alessio; Battisti, Matteo; Bertaina, Mario; Bolmgren, Karl; Cambiè, Giorgio; Casolino, Marco; Cassardo, Claudio; Cremonini, Roberto; Ferrarese, Silvia; Fuglesang, Christer; Manfrin, Massimiliano; Marcelli, Laura; et al. (Proceedings of 37th International Cosmic Ray Conference – PoS(ICRC2021), 2022)
Mini-EUSO is the first mission of the JEM-EUSO program located on the International Space Station. One of the main goals of the mission is to provide valuable scientific data in view of future large missions devoted to study Ultra-High Energy Cosmic Rays (UHECRs) from space by exploiting the fluorescence emission generated by Extensive Air Showers (EAS) developing in the atmosphere. A space mission like Mini-EUSO experiences continuous changes in atmospheric conditions, including the cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate as it might alter the instantaneous exposure for EAS detection or deteriorate the quality of the EAS images with consequences on the reconstructed EAS parameters. For this purpose, JEM-EUSO is planning to have an IR camera and a lidar as part of its Atmospheric Monitoring System. At the same time, it would be extremely beneficial if the UV camera itself would be able to detect the presence of clouds, at least in some specific conditions. For this reason, we analyze a few case studies by comparing the pixel count rates from Mini-EUSO during orbits with the cloud cover (as cloud fraction). This quantity is retrieved from the Global Forecast System (GFS) model at different height levels over the Mini-EUSO trajectory. The results of this analysis are reported.
CRIS-Team Scopus Importer:2022-12-23

BROADBAND SPECTROSCOPY USING TWO SUZAKU OBSERVATIONS OF THE HMXB GX 301-2 - Suchy, Slawomir; Fürst, Felix; Pottschmidt, Katja; Caballero, Isabel; Kreykenbohm, Ingo; Wilms, Jörn; Markowitz, Alex; Rothschild, Richard E. (Astrophysical Journal, 2012)
We present the analysis of two Suzaku observations of GX 301-2 at two orbital phases after the periastron passage. Variations in the column density of the line-of-sight absorber are observed, consistent with accretion from a clumpy wind. In addition to a cyclotron resonance scattering feature (CRSF), multiple fluorescence emission lines were detected in both observations. The variations in the pulse profiles and the CRSF throughout the pulse phase have a signature of a magnetic dipole field. Using a simple dipole model we calculated the expected magnetic field values for different pulse phases and were able to extract a set of geometrical angles, loosely constraining the dipole geometry in the neutron star. From the variation of the CRSF width and energy, we found a geometrical solution for the dipole, making the inclination consistent with previously published values.
Keywords: pulsars: individual (GX 301-2); stars: magnetic field; X-rays: binaries; X-rays: stars

Calibration aspects of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will be, after calibration, a very accurate instrument which yields the number of received photons from the number of measured photo-electrons. The project is in phase A (demonstration of the concept) including already operating prototype instruments, i.e. many parts of the instrument have been constructed and tested. Calibration is a crucial part of the instrument and its use. The focal surface (FS) of the JEM-EUSO telescope will consist of about 5000 photo-multiplier tubes (PMTs), which have to be well calibrated to reach the required accuracy in reconstructing the air-shower parameters. The optics system consists of 3 plastic Fresnel (double-sided) lenses of 2.5 m diameter. The aim of the calibration system is to measure the efficiencies (transmittances) of the optics and absolute efficiencies of the entire focal surface detector. The system consists of 3 main components: (i) Pre-flight calibration devices on ground, where the efficiency and gain of the PMTs will be measured absolutely and also the transmittance of the optics will be. (ii) On-board relative calibration system applying two methods: a) operating during the day when the JEM-EUSO lid will be closed with small light sources on board. b) operating during the night, together with data taking: the monitoring of the background rate over identical sites. (iii) Absolute in-flight calibration, again, applying two methods: a) measurement of the moon light, reflected on high altitude, high albedo clouds. b) measurements of calibrated flashes and tracks produced by the Global Light System (GLS). Some details of each calibration method will be described in this paper.
Keywords: Air-Shower fluorescence telescope; JEM-EUSO; Calibration; Space-Based experiment

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event - Kadler, Matthias; Krauss, Felicia; Mannheim, K.; Ojha, R.; Mueller, C.; Schulz, R.; Anton, Gisela; Baumgartner, W.; Beuchert, T.; Buson, S.; Carpenter, B.; Eberl, Thomas; et al. (Nature Physics, 2016)
The astrophysical sources of the extraterrestrial, very high-energy neutrinos detected by the IceCube collaboration remain to be identified. Gamma-ray (3-ray) blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the 3-ray photons are produced by accelerated protons in relativistic jets. As the background spectrum falls steeply with increasing energy, the individual events with the clearest signature of being of extraterrestrial origin are those at petaelectronvolt energies. Inside the large positional-uncertainty fields of the first two petaelectronvolt neutrinos detected by IceCube, the integrated emission of the blazar population has a sufficiently high electromagnetic flux to explain the detected IceCube events, but fluences of individual objects are too low to make an unambiguous source association. Here, we report that a major outburst of the blazar PKS B1424-418 occurred in temporal and positional coincidence with a third petaelectronvolt-energy neutrino event (HESE-35) detected by IceCube. On the basis of an analysis of the full sample of 3-ray blazars in the HESE-35 field, we show that the long-term average 3-ray emission of blazars as a class is in agreement with both the measured all-sky flux of petaelectronvolt neutrinos and the spectral slope of the IceCube signal. The outburst of PKS B1424-418 provides an energy output high enough to explain the observed petaelectronvolt event, suggestive of a direct physical association.

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Cosmic ray oriented performance studies for the JEM-EUSO first level trigger - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
JEM-EUSO is a space mission designed to investigate Ultra-High Energy Cosmic Rays and Neutrinos (E > 5.10(19) eV) from the International Space Station (ISS). Looking down from above its wide angle telescope is able to observe their air showers and collect such data from a very wide area. Highly specific trigger algorithms are needed to drastically reduce the data load in the presence of both atmospheric and human activity related background light, yet retain the rare cosmic ray events recorded in the telescope. We report the performance in offline testing of the first level trigger algorithm on data from JEM-EUSO prototypes and laboratory measurements observing different light sources: data taken during a high altitude balloon flight over Canada, laser pulses observed from the ground traversing the real atmosphere, and model landscapes reproducing realistic aspect ratios and light conditions as would be seen from the ISS itself. The first level trigger logic successfully kept the trigger rate within the permissible bounds when challenged with artificially produced as well as naturally encountered night sky background fluctuations and while retaining events with general air-shower characteristics. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: JEM-EUSO; Trigger system; FPGA; Nightglow background

Cyclotron lines in highly magnetized neutron stars - Staubert, R.; Truemper, J.; Kendziorra, E.; Klochkov, D.; Postnov, K.; Kretschmar, P.; Pottschmidt, K.; Haberl, F.; Rothschild, R. E.; Santangelo, A.; Wilms, Jörn; Kreykenbohm, Ingo; et al. (Astronomy & Astrophysics, 2019)
Cyclotron lines, also called cyclotron resonant scattering features are spectral features, generally appearing in absorption, in the X-ray spectra of objects containing highly magnetized neutron stars, allowing the direct measurement of the magnetic field strength in these objects. Cyclotron features are thought to be due to resonant scattering of photons by electrons in the strong magnetic fields. The main content of this contribution focusses on electron cyclotron lines as found in accreting X-ray binary pulsars (XRBP) with magnetic fields on the order of several 10(12) Gauss. Also, possible proton cyclotron lines from single neutron stars with even stronger magnetic fields are briefly discussed. With regard to electron cyclotron lines, we present an updated list of XRBPs that show evidence of such absorption lines. The first such line was discovered in a 1976 balloon observation of the accreting binary pulsar Hercules X-1, it is considered to be the first direct measurement of the magnetic field of a neutron star. As of today (end 2018), we list 35 XRBPs showing evidence of one ore more electron cyclotron absorption line(s). A few have been measured only once and must be confirmed (several more objects are listed as candidates). In addition to the Tables of objects, we summarize the evidence of variability of the cyclotron line as a function of various parameters (especially pulse phase, luminosity and time), and add a discussion of the di ff erent observed phenomena and associated attempts of theoretical modeling. We also discuss our understanding of the underlying physics of accretion onto highly magnetized neutron stars. For proton cyclotron lines, we present tables with seven neutron stars and discuss their nature and the physics in these objects.
Keywords: accretion; accretion disks; magnetic fields; radiation mechanisms: non-thermal; binaries: general; X-rays: binaries; stars: neutron

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Developments and results in the context of the JEM-EUSO program obtained with the ESAF simulation and analysis framework - Abe, S.; Adams, J. H.; Allard, D.; Alldredge, P.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Baret, B.; Barghini, D.; Battisti, M.; Bayer, J.; Bellotti, R.; et al. (European Physical Journal C: Particles and Fields, 2023)
JEM-EUSO is an international program for the development of space-based Ultra-High Energy Cosmic Ray observatories. The program consists of a series of missions which are either under development or in the data analysis phase. All instruments are based on a wide-field-of-view telescope, which operates in the near-UV range, designed to detect the fluorescence light emitted by extensive air showers in the atmosphere. We describe the simulation software ESAF in the framework of the JEM-EUSO program and explain the physical assumptions used. We present here the implementation of the JEM-EUSO, POEMMA, K-EUSO, TUS, Mini-EUSO, EUSO-SPB1 and EUSO-TA configurations in ESAF. For the first time ESAF simulation outputs are compared with experimental data.
CRIS-Team Scopus Importer:2023-11-24

ERASSt J040515.6-745202, an X-ray burster in the Magellanic Bridge - Haberl, F.; Vasilopoulos, G.; Maitra, C.; Valdes, F.; Lang, D.; Doroshenko, V.; Ducci, L.; Kreykenbohm, Ingo; Rau, A.; Weber, Philipp; Wilms, Jörn; Maggi, P.; et al. (Astronomy & Astrophysics, 2023)
Context. During the third all-sky survey (eRASS3), eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma, detected a new hard X-ray transient, eRASSt J040515.6-745202, in the direction of the Magellanic Bridge. Aims. We arranged follow-up observations and searched for archival data to reveal the nature of the transient. Methods. Using X-ray observations with XMM-Newton, NICER, and Swift, we investigated the temporal and spectral behaviour of the source for over about 10 days. Results. The X-ray light curve obtained from the XMM-Newton observation with an ∼28 ks exposure revealed a type-I X-ray burst with a peak bolometric luminosity of at least 1.4×1037 erg s-1. The burst energetics are consistent with a location of the burster at the distance of the Magellanic Bridge. The relatively long exponential decay time of the burst of ∼70 s indicates that it ignited in a H-rich environment. The non-detection of the source during the other eROSITA surveys, twelve and six months before and six months after eRASS3, suggests that the burst was discovered during a moderate outburst which reached 2.6×1036 erg s-1 in persistent emission. During the NICER observations, the source showed alternating flux states with the high level at a similar brightness as during the XMM-Newton observation. This behaviour is likely caused by dips as also seen during the last hour of the XMM-Newton observation. Evidence for a recurrence of the dips with a period of ∼21.8 h suggests eRASSt J040515.6-745202 is a low-mass X-ray binary (LMXB) system with an accretion disk seen nearly edge on.We identify a multi-wavelength counterpart to the X-ray source in UVW1 and g; r; i, and z images obtained by the optical/UV monitor on XMM-Newton and the Dark Energy Camera at the Cerro Tololo Inter-American Observatory. The spectral energy distribution is consistent with radiation from an accretion disk which dominates the UV and from a cool late-type star detected in the optical to infrared wavelengths. Conclusions. After the discovery of X-ray bursts inM31, the Magellanic Bridge is only the second location outside of the MilkyWay where an X-ray burster was found. The burst uniquely identifies eRASSt J040515.6-745202 as an LMXB system with a neutron star. Its location in the Magellanic Bridge confirms the existence of an older stellar population which is expected if the bridge was formed by tidal interactions between the Magellanic Clouds, which stripped gas and stars from the clouds.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Magellanic Clouds; Stars: mass-loss; Stars: neutron; X-rays: binaries; X-rays: bursts; X-rays: individuals: eRASSt J040515.6-745202

eROSITA detection of flares from the Be/X-ray binary A0538-66 - Ducci, L.; Mereghetti, S.; Santangelo, A.; Ji, L.; Carpano, S.; Covino, S.; Doroshenko; Haberl, F.; Maitra, C.; Kreykenbohm, Ingo; Udalski, A. (Astronomy & Astrophysics, 2022)
In 2018, XMM-Newton observed the awakening in X-rays of the Be/X-ray binary (Be/XRB) A0538-66. It showed bright and fast flares close to periastron with properties that had never been observed in other Be/XRBs before. We report the results from the observations of A0538-66 collected during the first all-sky survey of eROSITA, an X-ray telescope (0.2-10 keV) on board the Spektrum-RoentgenGamma satellite. eROSITA caught two flares within one orbital cycle at orbital phases phi = 0.29 and phi = 0.93 (where phi = 0 corresponds to periastron), with peak luminosities of similar to 2-4 x 10(36) erg s(-1) (0.2-10 keV) and durations of 42 <= Delta t(fl) <= 5.7 x 10(4) s. The flare observed at phi approximate to 0.29 shows that the neutron star can accrete considerably far from periastron, although it is expected to be outside of the circumstellar disk, thus providing important new information about the plasma environment surrounding the binary system. We also report the results from the photometric monitoring of A0538-66 carried out with the REM, OGLE, and MACHO telescopes from January 1993 until March 2020. We found that the two sharp peaks that characterize the orbital modulation in the optical occur asymmetrically in the orbit, relative to the position of the donor star.
CRIS-Team WoS Importer:2022-06-17
Keywords: accretion; accretion disks; stars: neutron; X-rays: binaries; X-rays: individuals: 1A 0538-66

eROSITA ground operations - Brunner, H.; Boller, T.; Coutinho, D.; Dauser, Thomas; Dennerl, K.; Dwelly, T.; Freyberg, M.; Fuermetz, M.; Georgakakis, A.; Grossberger, C.; Kreykenbohm, Ingo; Lamer, G.; et al. (2018)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on-board the Russian/German "Spectrum-Roentgen-Gamma"(SRG) mission. It will perform the first all-sky imaging X-ray survey in the medium X-ray energy band. eROSITA is currently awaiting its launch from Baikonur in early 2019 into an L2 halo orbit. Preparations for eROSITA ground operations have been under way in parallel with the hardware development of the eROSITA telescope, comprising the areas mission planning, telescope operation and data reception, the operation of a data processing pipeline, and the creation of tools for data access and interactive data analysis. eROSITA mission: After a brief calibration and performance verification phase eROSITA will perform a four-year all-sky survey fully covering the sky eight times, which will be followed by several years of dedicated observations of interesting objects. Two ground antennas in Russia (near Moscow and in Siberia) will be available to provide several hours of daily ground contact for commanding and for data reception. eROSITA data rights will be equally divided between the Russian and German partners. Operation and data centers will exist at Max-Planck-Institut fur extraterrestrische Physics (MPE) in Garching, Germany and at the Russian Space Research Institute (IKI) in Moscow. Interfaces and procedures for mission planning, telescope operation and data exchange are closely coordinated between both sites. Mission planning and operation: Based on orbit simulations provided by the Russian side, a software environment for optimizing the desired sky coverage and observing efficiency while fulfilling visibility and solar constraints was set up. Agreed upon observing timelines will be converted to eROSITA and SRG command sequences fed to the Russian ground station for up-linking. MPE personnel will be on site either in Moscow or at MPE in Garching during each ground contact to conduct on-demand commanding and to assess instrument health and data quality. Data analysis pipeline and interactive data analysis: The eROSITA data processing pipeline consists of modules for data ingestion, event calibration, exposure calculation, source detection, and the creation of high-level source specific data products. It will be operated at MPE on a daily basis after each ground contact. A subset of the software tasks comprising the data analysis pipeline also functions as interactive data analysis tools. These can be grouped into tasks for X-ray event calibration, selection and binning, exposure, background and sensitivity map creation and for source detection. Data products are provided in a standards compliant FITS format for use with well-known high-level X-ray data analysis tools. A Web based graphical source catalog and data products viewer will allow easy data browsing. Since mid-2014 the interactive eROSITA data analysis package is available to the eROSITA user community, permitting the analysis of simulated eROSITA datasets, created by a sophisticated X-ray modeling and simulation tool.
Keywords: eROSITA; SRG; Spectrum-Roentgen-Gamma; X-ray telescope; space telescope; all-sky survey; astrophysics; ground segment

EROSITA on SRG - Predehl, Peter; Andritschke, Robert; Babyshkin, Vladimir; Becker, Werner; Bornemann, Walter; Bräuninger, Heinrich; Brunner, Hermann; Boller, Thomas; Burwitz, Vadim; Burkert, Wolfgang; Clerc, Nicolas; Churazov, Eugene; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the core instrument on the Russian/German Spektrum-Roentgen-Gamma (SRG) mission which is now officially scheduled for launch on September 2017, eROSITA will perform a deep survey of the entire X-ray sky. Within the first 4 years of the mission the sky will be scanned 8 times. In the soft band (0.5-2 keV), it will be about 30 times more sensitive than ROSAT, while in the hard band (2-8 keV) it will provide the first ever true imaging survey of the sky. eROSITA is currently (June 2016) in its final integration and test phase. All seven FM Mirror Assemblies and Camera Assemblies (+ 1 spare) have been tested and calibrated. All subsystems and components are well within their expected performances.
Keywords: eROSITA; X-ray astronomy; X-ray optics; X-ray telescopes; X-ray testing

Erratum to “Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope” [Phys. Lett. B 769 (2017)249–254](S037026931730254X)(10.1016/j.physletb.2017.03.063) - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2019)
Limits on the neutrino flux for a given mass [Formula presented] and annihilation channel are calculated as in Eq. (7)(page 252), with the integrated acceptances defined in Eq. (8)(page 252)as the effective area averaged over the neutrino energy. A numerical approximation of WIMP annihilation spectra, adapted from [1]with a too coarse binning, led to an overestimation of the integrated acceptances for dark-matter induced neutrino events. The spectra were replaced with a fine-binned version both in the likelihood and in the acceptances. The main change is a weaker limit for WIMP masses larger than 1 TeV/ [Formula presented]. Updated versions of Figs. 3–6 are provided.
CRIS-Team Scopus Importer:2019-06-04

EUSO-SPB1 mission and science - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Pernas, M. Ave; et al. (Astroparticle Physics, 2024)
The Extreme Universe Space Observatory on a Super Pressure Balloon 1 (EUSO-SPB1) was launched in 2017 April from Wanaka, New Zealand. The plan of this mission of opportunity on a NASA super pressure balloon test flight was to circle the southern hemisphere. The primary scientific goal was to make the first observations of ultra-high-energy cosmic-ray extensive air showers (EASs) by looking down on the atmosphere with an ultraviolet (UV) fluorescence telescope from suborbital altitude (33 km). After 12 days and 4 h aloft, the flight was terminated prematurely in the Pacific Ocean. Before the flight, the instrument was tested extensively in the West Desert of Utah, USA, with UV point sources and lasers. The test results indicated that the instrument had sensitivity to EASs of ⪆3 EeV. Simulations of the telescope system, telescope on time, and realized flight trajectory predicted an observation of about 1 event assuming clear sky conditions. The effects of high clouds were estimated to reduce this value by approximately a factor of 2. A manual search and a machine-learning-based search did not find any EAS signals in these data. Here we review the EUSO-SPB1 instrument and flight and the EAS search.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Air fluorescence; Cosmic rays (329); Extensive air showers; High-altitude balloons (738); JEM-EUSO

EUSO-SPB2 Telescope Optics and Testing - Kungel, Viktoria; Bachman, Randy; Brewster, Jerod; Dawes, Madeline; Desiato, Julianna; Eser, Johannes; Finch, William; Huelett, Lindsey; Olinto, Angela V.; Pace, Justin; Pech, Miroslav; Reardon, Patrick; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory - Super Pressure Balloon (EUSO-SPB2) mission will fly two custom telescopes that feature Schmidt optics to measure Čerenkov- and fluorescence-emission of extensive air-showers from cosmic rays at the PeV and EeV-scale, and search for τ-neutrinos. Both telescopes have 1-meter diameter apertures and UV/UV-visible sensitivity. The Čerenkov telescope uses a bifocal mirror segment alignment, to distinguish between a direct cosmic ray that hits the camera versus the Čerenkov light from outside the telescope. Telescope integration and laboratory calibration will be performed in Colorado. To estimate the point spread function and efficiency of the integrated telescopes, a test beam system that delivers a 1-meter diameter parallel beam of light is being fabricated. End-to-end tests of the fully integrated instruments will be carried out in a field campaign at dark sites in the Utah desert using cosmic rays, stars, and artificial light sources. Laser tracks have long been used to characterize the performance of fluorescence detectors in the field. For EUSO-SPB2 an improvement in the method that includes a correction for aerosol attenuation is anticipated by using a bi-dynamic Lidar configuration in which both the laser and the telescope are steerable. We plan to conduct these field tests in Fall 2021 and Spring 2022 to accommodate the scheduled launch of EUSO-SPB2 in 2023 from Wanaka, New Zealand.
CRIS-Team Scopus Importer:2024-12-16

EUSO-TA - First results from a ground-based EUSO telescope - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2018)
EUSO-TA is a ground-based telescope, installed at the Telescope Array (TA) site in Black Rock Mesa, Utah, USA. This is the first detector to successfully use a Fresnel lens based optical system and multi-anode photomultipliers (64 channels per tube, 2304 channels encompassing a 10.6 degrees x 10.6 degrees field of view) for detection of Ultra High Energy Cosmic Rays (UHECR). The telescope is located in front of one of the fluorescence detectors of the TA experiment. Since its installation in 2013, the detector has observed several ultra-high energy cosmic ray events and, in addition, meteors. The limiting magnitude of 5.5 on summed frames (similar to 3 ms) has been established. Measurements of the UV night sky emission in different conditions and moon phases and positions have been completed. The performed observations serve as a proof of concept for the future application of this detector technology. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: UHECR; EAS; JEM-EUSO; cosmic rays; Fresnel lens

Evidence for different accretion regimes in GRO J1008-57 - Kühnel, Matthias; Furst, Felix; Pottschmidt, Katja; Kreykenbohm, Ingo; Ballhausen, Ralf; Falkner, Sebastian; Rothschild, Richard E.; Klochkov, Dmitry; Wilms, Jörn (Astronomy & Astrophysics, 2017)
We present a comprehensive spectral analysis of the BeXRB GRO J1008-57 over a luminosity range of three orders of magnitude using NuSTAR, Suzaku, and RXTE data. We find significant evolution of the spectral parameters with luminosity. In particular, the photon index hardens with increasing luminosity at intermediate luminosities in the range 10(36)-10(37) erg s(-1). This evolution is stable and repeatedly observed over different outbursts. However, at the extreme ends of the observed luminosity range, we find that the correlation breaks down, with a significance level of at least 3.7 sigma. We conclude that these changes indicate transitions to different accretion regimes, which are characterized by different deceleration processes, such as Coulomb or radiation breaking. We compare our observed luminosity levels of these transitions to theoretical predications and discuss the variation of those theoretical luminosity values with fundamental neutron star parameters. Finally, we present detailed spectroscopy of the unique "triple peaked" outburst in 2014/15 which does not fit in the general parameter evolution with luminosity. The pulse profile on the other hand is consistent with what is expected at this luminosity level, arguing against a change in accretion geometry. In summary, GRO J1008-57 is an ideal target to study different accretion regimes due to the well-constrained evolution of its broad-band spectral continuum over several orders of magnitude in luminosity.
Keywords: X-rays: binaries; stars: neutron; stars: emission-line; Be; pulsars: individual: GRO J1008-57

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Expected Performance of the EUSO-SPB2 Fluorescence Telescope - Heaton, C.; Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory Super Pressure Balloon 2 (EUSO-SPB2) is under development, and will prototype instrumentation for future satellite-based missions, including the Probe of Extreme Multi-Messenger Astrophysics (POEMMA). EUSO-SPB2 will consist of two telescopes. The first is a Cherenkov telescope (CT) being developed to identify and estimate the background sources for future below-the-limb very high energy (E>10 PeV) astrophysical neutrino observations, as well as above-the-limb cosmic ray induced signals (E>1 PeV). The second is a fluorescence telescope (FT) being developed for detection of Ultra High Energy Cosmic Rays (UHECRs). In preparation for the expected launch in 2023, extensive simulations tuned by preliminary laboratory measurements have been performed to understand the FT capabilities. The energy threshold has been estimated at 1018.2 eV, and results in a maximum detection rate at 1018.6 eV when taking into account the shape of the UHECR spectrum. In addition, onboard software has been developed based on the simulations as well as experience with previous EUSO missions. This includes a level 1 trigger to be run on the computationally limited flight hardware, as well as a deep learning based prioritization algorithm in order to accommodate the balloon's telemetry budget. These techniques could also be used later for future, space-based missions.
CRIS-Team Scopus Importer:2024-12-16

Expected performance of the K-EUSO space-based observatory - Bianciotto, Marta; Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; et al. (Proceedings of Science, 2022)
K-EUSO is a planned mission of the JEM-EUSO program for the study of ultra-high energy cosmic rays (UHECR) from space, to be deployed on the International Space Station. The K-EUSO observatory consists of a UV telescope with a wide field of view, which aims at the detection of fluorescence light emitted by extensive air showers (EAS) in the atmosphere. The EAS events will be sampled with a time resolution of 1-2.5 μs to reconstruct the entire shower profile with high precision. The detector consisting of ∼ 105 independent pixels will allow a spatial resolution of ∼700 m on ground. From a 400 km altitude, K-EUSO will achieve a large and full sky exposure to sample the highest energy range of the UHECR spectrum. In this contribution, we present estimates of the performance of the observatory: an estimation of the expected exposure and triggered event rate as a function of energy and the event reconstruction performance, including resolution of arrival directions and energy of UHECRs.
CRIS-Team Scopus Importer:2024-12-16

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First observations of speed of light tracks by a fluorescence detector looking down on the atmosphere - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Journal of Instrumentation, 2018)
EUSO-Balloon is a pathfinder mission for the Extreme Universe Space Observatory onboard the Japanese Experiment Module (JEM-EUSO). It was launched on the moonless night of the 25(th) of August 2014 from Timmins, Canada. The flight ended successfully after maintaining the target altitude of 38 km for five hours. One part of the mission was a 2.5 hour underflight using a helicopter equipped with three UV light sources (LED, xenon flasher and laser) to perform an inflight calibration and examine the detectors capability to measure tracks moving at the speed of light. We describe the helicopter laser system and details of the underflight as well as how the laser tracks were recorded and found in the data. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. Finally, we present a first reconstruction of the direction of the laser tracks relative to the detector.
Keywords: Detectors for UV; visible and IR photons; Lasers; Balloon instrumentation; Space instrumentation

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

GRO J1008-57: an (almost) predictable transient X-ray binary - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, F.; Pottschmidt, K.; Rothschild, R. E.; Caballero, I.; Grinberg, Victoria; Schoenherr, G.; Shrader, C.; Klochkov, D.; Staubert, R.; et al. (Astronomy & Astrophysics, 2013)
A study of archival RXTE, Swift, and Suzaku pointed observations of the transient high-mass X-ray binary GRO J1008-57 is presented. A new orbital ephemeris based on pulse arrival-timing shows the times of maximum luminosities during outbursts of GRO J1008-57 to be close to periastron at orbital phase -0.03. This makes the source one of a few for which outburst dates can be predicted with very high precision. Spectra of the source in 2005, 2007, and 2011 can be well described by a simple power law with high-energy cutoff and an additional black body at lower energies. The photon index of the power law and the black-body flux only depend on the 15-50 keV source flux. No apparent hysteresis effects are seen. These correlations allow us to predict the evolution of the pulsar's X-ray spectral shape over all outbursts as a function of just one parameter, the source's flux. If modified by an additional soft component, this prediction even holds during GRO J1008-57's 2012 type II outburst.
Keywords: X-rays: binaries; pulsars: individual: GRO J1008-57; accretion; accretion disks; ephemerides

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

High variability in Vela X-1: giant flares and off states - Kreykenbohm, Ingo; Wilms, Jörn; Kretschmar, Peter; Torrejon, J. M.; Pottschmidt, K.; Hanke, Manfred; Santangelo, A.; Ferrigno, Carlo; Staubert, R. (Astronomy & Astrophysics, 2008)
Aims. We investigate the spectral and temporal behavior of the high mass X-ray binary Vela X-1 during a phase of high activity, with special focus on the observed giant flares and off states.Methods. INTEGRAL observed Vela X-1 in a long almost uninterrupted observation for two weeks in 2003 Nov/Dec. The data were analyzed with OSA 7.0 and FTOOLS 6.2. We derive the pulse period, light curves, spectra, hardness ratios, and hardness intensity diagrams, and study the eclipse.Results. In addition to an already high activity level, Vela X-1 exhibited several intense flares, the brightest ones reaching a maximum intensity of more than 5 Crab in the 20-40 keV band and several off states where the source was no longer detected by INTEGRAL. We determine the pulse period to be 283.5320 +/- 0.0002 s, which is stable throughout the entire observation. Analyzing the eclipses provided an improvement in the ephemeris. Spectral analysis of the flares indicates that there appear to be two types of flares: relatively brief flares, which can be extremely intense and show spectral softening, in contrast to high intensity states, which are longer and show no softening.Conclusions. Both flares and off states are interpreted as being due to a strongly structured wind of the optical companion. When Vela X-1 encounters a cavity with strongly reduced density, the flux will drop triggering the onset of the propeller effect, which inhibits further accretion, giving rise to off states. The sudden decrease in the density of the material required to trigger the propeller effect in Vela X-1 is of the same order as predicted by theoretical papers about the densities in OB star winds. A similarly structured wind can produce giant flares when Vela X-1 encounters a dense blob in the wind.
Keywords: X-rays: stars; stars: flare; stars: pulsars: individual: Vela X-1; stars: magnetic fields

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Long-term spectral study of the black hole Cygnus X-1 using INTEGRAL - Cangemi, F.; Beuchert, T.; Siegert, T.; Grinberg, V.; Wilms, Jörn; Rodriguez, J.; Kreykenbohm, Ingo; Laurent, P.; Pottschmidt, K. (Memorie della Societa Astronomica Italiana - Journal of the Italian Astronomical Society, 2019)
We utilize the joint capabilities of IBIS and SPI to perform a state-resolved 20-2000 keV analysis of the microquasar Cygnus X-1. In both LHS and HSS, the spectral analysis reveals the presence of a high-energy tail above 400 keV in addition to a standard, Compton-like continuum in the 20-400 keV range. We study the polarisation properties of the hard X-ray radiation, as well as of the polarisation of this high-energy tail. Polarisation is detected in the LHS in agreement with previous work. We find potential variations of the LHS polarisation with time and no polarisation detection in the HSS.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cygnus X-1; INTEGRAL; X-rays binaries

Long-term variability of Vela X-1 - Kretschmar, Peter; Keating, J.; Kreykenbohm, Ingo; Wilms, Jörn; Staubert, R. (2010)
The archetypical wind-accreting X-ray pulsar Vela X-1 is known to be variable on a large range of timescales. Relatively tranquil phases exist as well as extended phases of high variability and flaring. We present results from a systematic study of variations with orbital phase and other timescales based on RXTE/ASM and Swift/BAT data.
Keywords: X-rays: binaries; Stars: neutron; Stars: winds; outflows

Luminosity dependent accretion state change in GRO J1008-57 - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, Felix; Pottschmidt, Katja; Rothschild, Richard E.; Caballero, Isabel; Grinberg, Victoria; Schoenherr, Gabriele; Shrader, Chris; Klochkov, Dmitry; Staubert, Ruediger; et al. (2014)
In a former publication, we have analyzed the transient neutron star X-ray binary GRO J1008-57 using all available RXTE-, Swift-, and Suzaku-data. As we have found, the source's spectral components, i.e., a power-law with high exponential cutoff and a black-body, are strongly correlated with the hard X-ray flux (15-50 keV). We update the analytical description of these dependence, including a change in the photon index behaviour from a flat to a logarithmic function. The flux, where the change occurs, is consistent with the onset of the black-body emission. Thus, a change of the accretion state always occurs in GRO J1008-57 at a particular flux level.

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Meteor studies in the framework of the JEM-EUSO program - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H. J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We summarize the state of the art of a program of UV observations from space of meteor phenomena, a secondary objective of the JEM-EUSO international collaboration. Our preliminary analysis indicates that JEM-EUSO, taking advantage of its large FOV and good sensitivity, should be able to detect meteors down to absolute magnitude close to 7. This means that JEM-EUSO should be able to record a statistically significant flux of meteors, including both sporadic ones, and events produced by different meteor streams. Being unaffected by adverse weather conditions, JEM-EUSO can also be a very important facility for the detection of bright meteors and fireballs, as these events can be detected even in conditions of very high sky background. In the case of bright events, moreover, exhibiting some persistence of the meteor train, preliminary simulations show that it should be possible to exploit the motion of the ISS itself and derive at least a rough 3D reconstruction of the meteor trajectory. Moreover, the observing strategy developed to detect meteors may also be applied to the detection of nuclearites, exotic particles whose existence has been suggested by some theoretical investigations. Nuclearites are expected to move at higher velocities than meteoroids, and to exhibit a wider range of possible trajectories, including particles moving upward after crossing the Earth. Some pilot studies, including the approved Mini-EUSO mission, a precursor of JEM-EUSO, are currently operational or in preparation. We are doing simulations to assess the performance of Mini-EUSO for meteor studies, while a few meteor events have been already detected using the ground-based facility EUSO-TA.
Keywords: Meteors; Nuclearites; JEM-EUSO; Mini-EUSO; EUSO-TA

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multi-wavelength study of Mrk 421 during a TeV flare - Gokus, Andrea; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Dauser, Thomas; Dorner, D.; Elsaesser, D.; Eppel, F.; Heßdörfer, J.; Kadler, M.; Kraus, A.; Kreter, M.; et al. (Proceedings of Science, 2022)
The blazar Mrk 421 shows frequent, short flares in the TeV energy regime. Due to the fast nature of such episodes, we often fail to obtain sufficient simultaneous information about flux variations in several energy bands. To overcome this lack of multi-wavelength (MWL) coverage, especially for the pre- and post-flare periods, we have set up a monitoring program with the FACT telescope (TeV energies) and the Neil Gehrels Swift Observatory (X-rays). On 2019 June 9, Mrk 421 showed a TeV outburst reaching a flux level of more than two times the flux of the Crab Nebula at TeV energies. We acquired simultaneous data in the X-rays with additional observations by XMM-Newton and INTEGRAL. For the first time, we can study a TeV blazar in outburst taking advantage of highly sensitive X-ray data from XMM-Newton and INTEGRAL combined. Our dataset is complemented by pointed radio observations by Effelsberg at GHz frequencies. We present our first results, including the γ-ray and X-ray light curves, a timing analysis of the X-ray data obtained with XMM-Newton , as well as the radio spectra before, during and after the flare.
CRIS-Team Scopus Importer:2022-12-23

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

Neutrino Target-of-Opportunity Observations with Space-based and Suborbital Optical Cherenkov Detectors - Venters, Tonia M.; Reno, Mary Hall; Krizmanic, John F.; Olinto, A. V.; Adams, J. H.; Aloisio, R.; Anchordoqui, L. A.; Anzalone, A.; Bagheri, M.; Barghini, D.; Battisti, M.; Bergman, D. R.; et al. (Proceedings of Science, 2022)
Cosmic-ray accelerators capable of reaching ultra-high energies are expected to also produce very-high energy neutrinos via hadronic interactions within the source or its surrounding environment. Many of the candidate astrophysical source classes are either transient in nature or exhibit flaring activity. Using the Earth as a neutrino converter, suborbital and space-based optical Cherenkov detectors, such as POEMMA and EUSO-SPB2, will be able to detect upward-moving extensive air showers induced by decaying tau-leptons generated from cosmic tau neutrinos with energies ∼ 10 PeV and above. Both EUSO-SPB2 and POEMMA will be able to quickly repoint, enabling rapid response to astrophysical transient events. We calculate the transient sensitivity and sky coverage for both EUSO-SPB2 and POEMMA, accounting for constraints imposed by the Sun and the Moon on the observation time. We also calculate both detectors' neutrino horizons for a variety of modeled astrophysical neutrino fluences. We find that both EUSO-SPB2 and POEMMA will achieve transient sensitivities at the level of modeled neutrino fluences for nearby sources. We conclude with a discussion of the prospects of each mission detecting at least one transient event for various modeled astrophysical neutrino sources.
CRIS-Team Scopus Importer:2024-12-16

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Observatory science with eXTP - In'T Zand, Jean J. M.; Bozzo, Enrico; Qu, Jinlu; Li, Xiang-Dong; Amati, Lorenzo; Chen, Yang; Donnarumma, Immacolata; Doroshenko, Victor; Drake, Stephen A.; Hernanz, Margarita; Jenke, Peter A.; Maccarone, Thomas J.; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this White Paper we present the potential of the enhanced X-ray Timing and Polarimetry (eXTP) mission for studies related to Observatory Science targets. These include flaring stars, supernova remnants, accreting white dwarfs, low and high mass X-ray binaries, radio quiet and radio loud active galactic nuclei, tidal disruption events, and gamma-ray bursts. eXTP will be excellently suited to study one common aspect of these objects: their often transient nature. Developed by an international Consortium led by the Institute of High Energy Physics of the Chinese Academy of Science, the eXTP mission is expected to be launched in the mid 2020s.
Keywords: space research instruments; nuclear astrophysics; flare stars; accretion and accretion disks; mass loss and stellar winds; cataclysmic binaries; X-ray binaries; supernova remnants; active galactic nuclei; X-ray bursts; gamma-ray bursts; gravitational waves

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Outburst of GX 304-1 monitored with INTEGRAL: positive correlation between the cyclotron line energy and flux - Klochkov, D.; Doroshenko, Victor; Santangelo, A.; Staubert, R.; Ferrigno, Carlo; Kretschmar, Peter; Caballero, I.; Wilms, Jörn; Kreykenbohm, Ingo; Pottschmidt, K.; Rothschild, R. E.; Wilson-Hodge, C. A.; et al. (Astronomy & Astrophysics, 2012)
Context. X-ray spectra of many accreting pulsars exhibit significant variations as a function of flux and thus of mass accretion rate. In some of these pulsars, the centroid energy of the cyclotron line(s), which characterizes the magnetic field strength at the site of the X-ray emission, has been found to vary systematically with flux.Aims. GX304-1 is a recently established cyclotron line source with a line energy around 50 keV. Since 2009, the pulsar shows regular outbursts with the peak flux exceeding one Crab. We analyze the INTEGRAL observations of the source during its outburst in January-February 2012.Methods. The observations covered almost the entire outburst, allowing us to measure the source's broad-band X-ray spectrum at different flux levels. We report on the variations in the spectral parameters with luminosity and focus on the variations in the cyclotron line.Results. The centroid energy of the line is found to be positively correlated with the luminosity. We interpret this result as a manifestation of the local sub-Eddington (sub-critical) accretion regime operating in the source.
Keywords: X-rays: binaries; stars: neutron; accretion; accretion disks

Performances of JEM-EUSO: angular reconstruction (vol 30, pg 153, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Performances of JEM-EUSO: energy and X (max) reconstruction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory (EUSO) on-board the Japanese Experimental Module (JEM) of the International Space Station aims at the detection of ultra high energy cosmic rays from space. The mission consists of a UV telescope which will detect the fluorescence light emitted by cosmic ray showers in the atmosphere. The mission, currently developed by a large international collaboration, is designed to be launched within this decade. In this article, we present the reconstruction of the energy of the observed events and we also address the X (max) reconstruction. After discussing the algorithms developed for the energy and X (max) reconstruction, we present several estimates of the energy resolution, as a function of the incident angle, and energy of the event. Similarly, estimates of the X (max) resolution for various conditions are presented.
Keywords: JEM-EUSO; Energy reconstruction; X-max reconstruction

Potential origin of the state-dependent high-energy tail in the black hole microquasar Cygnus X-1 as seen with INTEGRAL - Cangemi, F.; Beuchert, T.; Siegert, T.; Rodriguez, J.; Grinberg, V.; Belmont, R.; Gouiffès, C.; Kreykenbohm, Ingo; Laurent, P.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. 0.1-10 MeV observations of the black hole microquasar Cygnus X-1 have shown the presence of a spectral feature in the form of a power law in addition to the standard black body (0.1-10 keV) and Comptonization (10-200 keV) components observed by INTEGRAL in several black-hole X-ray binaries. This so-called "high-energy tail"was recently shown to be strong in the hard spectral state of Cygnus X-1, and, in this system, has been interpreted as the high-energy part of the emission from a compact jet. Aims. This result was nevertheless obtained from a data set largely dominated by hard state observations. In the soft state, only upper limits on the presence and hence the potential parameters of a high-energy tail could be derived. Using an extended data set, we aim to obtain better constraints on the properties of this spectral component in both states. Methods. We make use of data obtained from about 15 years of observations with the INTEGRAL satellite. The data set is separated into the different states and we analyze stacked state-resolved spectra obtained from the X-ray monitors, the gamma-ray imager, and the gamma-ray spectrometer (SPI) onboard. Results. A high-energy component is detected in both states, confirming its earlier detection in the hard state and its suspected presence in the soft state with INTEGRAL, as seen in a much smaller SPI data set. We first characterize the high-energy tail components in the two states through a model-independent, phenomenological analysis. We then apply physical models based on hybrid Comptonization (eqpair and belm). The spectra are well modeled in all cases, with a similar goodness of the fits. While in the semi-phenomenological approach the high-energy tail has similar indices in both states, the fits with the physical models seem to indicate slightly different properties. Based on this approach, we discuss the potential origins of the high-energy components in both the soft and hard states, and favor an interpretation where the high-energy component is due to a compact jet in the hard state and hybrid Comptonization in either a magnetized or nonmagnetized corona in the soft state.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Accretion; accretion disks; Black hole physics; Radiation mechanisms: non-thermal; X-rays: binaries; X-rays: individuals: Cyg X-1

Rapid variability of Markarian 421 during extreme flaring as seen through the eyes of XMM-Newton - Gokus, A.; Wilms, Jörn; Kadler, M.; Dorner, D.; Nowak, M. A.; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Schleicher, B.; Markowitz, A. G.; Pottschmidt, K.; Mannheim, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
By studying the variability of blazars across the electromagnetic spectrum, it is possible to resolve the underlying processes responsible for rapid flux increases, so-called flares. We report on an extremely bright X-ray flare in the high-peaked BL Lacertae object Markarian 421 (Mrk 421) that occurred simultaneously with enhanced γ-ray activity detected at very high energies by First G-APD Cherenkov Telescope on 2019 June 9. We triggered an observation with XMM-Newton, which observed the source quasi-continuously for 25 h. We find that the source was in the brightest state ever observed using XMM-Newton, reaching a flux of 2.8 × 10-9 over an energy range of 0.3-10 keV. We perform a spectral and timing analysis to reveal the mechanisms of particle acceleration and to search for the shortest source-intrinsic time-scales. Mrk 421 exhibits the typical harder-when-brighter behaviour throughout the observation and shows a clock-wise hysteresis pattern, which indicates that the cooling dominates over the acceleration process. While the X-ray emission in different sub-bands is highly correlated, we can exclude large time lags as the computed z-transformed discrete correlation functions are consistent with a zero lag. We find rapid variability on time-scales of 1 ks for the 0.3-10 keV band and down to 300 s in the hard X-ray band (4-10 keV). Taking these time-scales into account, we discuss different models to explain the observed X-ray flare, and find that a plasmoid-dominated magnetic reconnection process is able to describe our observation best.
CRIS-Team Scopus Importer:2024-03-29
Keywords: acceleration of particles; BL Lacertae objects: individual: Markarian 421; galaxies: active; relativistic processes; X-rays: galaxies

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

RXTE observations of the 1A 1118-61 in an outburst, and the discovery of a cyclotron line - Doroshenko, Victor; Suchy, S.; Santangelo, A.; Staubert, R.; Kreykenbohm, Ingo; Rothschild, R.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2010)
We present the analysis of RXTE monitoring data obtained during the 2009 January outburst of the hard X-ray transient 1A 1118-61. Using these observations the broadband (3.5-120 keV) spectrum of the source was measured for the first time ever. We have found that the broadband continuum spectrum of the source is similar to other accreting pulsars and is well described by several conventionally used phenomenological models. We have discovered that regardless of the applied continuum model, a prominent broad absorption feature at similar to 55 keV is observed. We interpret this feature as a cyclotron resonance scattering feature (CRSF). The observed CRSF energy is one of the highest known and corresponds to a magnetic field of B similar to 4.8 x 10(12) G in the scattering region. Our data also indicate the presence of an iron emission line presence that has not been previously reported for 1A 1118-61. Timing properties of the source, including a strong spin-up, were found to be similar to those observed by CGRO/BATSE during the previous outburst, but the broadband capabilities of RXTE reveal a more complicated energy dependency of the pulse-profile.
Keywords: stars: neutron; pulsars: individual: 1A 1118-61; binaries: general

Science and mission status of EUSO-SPB2 - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory on a Super Pressure Balloon II (EUSO-SPB2) is a second generation stratospheric balloon instrument for the detection of Ultra High Energy Cosmic Rays (UHECRs, E > 1 EeV) via the fluorescence technique and of Very High Energy (VHE, E > 10 PeV) neutrinos via Cherenkov emission. EUSO-SPB2 is a pathfinder mission for instruments like the proposed Probe Of Extreme Multi-Messenger Astrophysics (POEMMA). The purpose of such a space-based observatory is to measure UHECRs and UHE neutrinos with high statistics and uniform exposure. EUSO-SPB2 is designed with two Schmidt telescopes, each optimized for their respective observational goals. The Fluorescence Telescope looks at the nadir to measure the fluorescence emission from UHECR-induced extensive air shower (EAS), while the Cherenkov Telescope is optimized for fast signals (∼10 ns) and points near the Earth's limb. This allows for the measurement of Cherenkov light from EAS caused by Earth skimming VHE neutrinos if pointed slightly below the limb or from UHECRs if observing slightly above. The expected launch date of EUSO-SPB2 is Spring 2023 from Wanaka, NZ with target duration of up to 100 days. Such a flight would provide thousands of VHECR Cherenkov signals in addition to tens of UHECR fluorescence tracks. Neither of these kinds of events have been observed from either orbital or suborbital altitudes before, making EUSO-SPB2 crucial to move forward towards a space-based instrument. It will also enhance the understanding of potential background signals for both detection techniques. This contribution will provide a short overview of the detector and the current status of the mission as well as its scientific goals.
CRIS-Team Scopus Importer:2024-12-16

Science of atmospheric phenomena with JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The main goal of the JEM-EUSO experiment is the study of Ultra High Energy Cosmic Rays (UHECR, 10(19)-10(21) e V), but the method which will be used (detection of the secondary light emissions induced by cosmic rays in the atmosphere) allows to study other luminous phenomena. The UHECRs will be detected through the measurement of the emission in the range between 290 and 430 m, where some part of Transient Luminous Events (TLEs) emission also appears. This work discusses the possibility of using the JEM-EUSO Telescope to get new scientific results on TLEs. The high time resolution of this instrument allows to observe the evolution of TLEs with great precision just at the moment of their origin. The paper consists of four parts: review of the present knowledge on the TLE, presentation of the results of the simulations of the TLE images in the JEM-EUSO telescope, results of the Russian experiment Tatiana-2 and discussion of the possible progress achievable in this field with JEM-EUSO as well as possible cooperation with other space projects devoted to the study of TLE - TARANIS and ASIM. In atmospheric physics, the study of TLEs became one of the main physical subjects of interest after their discovery in 1989. In the years 1992 - 1994 detection was performed from satellite, aircraft and space shuttle and recently from the International Space Station. These events have short duration (milliseconds) and small scales (km to tens of km) and appear at altitudes 50 - 100 km. Their nature is still not clear and each new experimental data can be useful for a better understanding of these mysterious phenomena.
Keywords: Transient Luminous Events; Elves; Sprites; Jets - Atmospheric phenomena

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for magnetic monopoles with ten years of the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Astrophysics, 2022)
This work presents a new search for magnetic monopoles using data taken with the ANTARES neutrino telescope over a period of 10 years (January 2008 to December 2017). Compared to previous ANTARES searches, this analysis uses a run-by-run simulation strategy, with a larger exposure as well as a new simulation of magnetic monopoles taking into account the Kasama, Yang and Goldhaber model for their interaction cross-section with matter. No signal compatible with the passage of relativistic magnetic monopoles is observed, and upper limits on the flux of magnetic monopoles with β=v/c≥0.55, are presented. For ultra-relativistic magnetic monopoles the flux limit is ∼7×10−18 cm−2s−1sr−1.
CRIS-Team Scopus Importer:2022-03-25
Keywords: ANTARES telescope; Magnetic monopoles; Neutrino

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for non-standard neutrino interactions with 10 years of ANTARES data - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2022)
Non-standard interactions of neutrinos arising in many theories beyond the Standard Model can significantly alter matter effects in atmospheric neutrino propagation through the Earth. In this paper, a search for deviations from the prediction of the standard 3-flavour atmospheric neutrino oscillations using the data taken by the ANTARES neutrino telescope is presented. Ten years of atmospheric neutrino data collected from 2007 to 2016, with reconstructed energies in the range from ∼16 GeV to 100 GeV, have been analysed. A log-likelihood ratio test of the dimensionless coefficients εμτ and εττ − εμμ does not provide clear evidence of deviations from standard interactions. For normal neutrino mass ordering, the combined fit of both coefficients yields a value 1.7σ away from the null result. However, the 68% and 95% confidence level intervals for εμτ and εττ − εμμ, respectively, contain the null value. Best fit values, one standard deviation errors and bounds at the 90% confidence level for these coefficients are given for both normal and inverted mass orderings. The constraint on εμτ is among the most stringent to date and it further restrains the strength of possible non-standard interactions in the μ − τ sector. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-22
Keywords: Neutrino Detectors and Telescopes (experiments)

Search for nuclearites with the ANTARES detector - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Proceedings of Science, 2022)
ANTARES is a Cherenkov underwater neutrino telescope operating in the Mediterranean. Its construction was completed in 2008. Even though optimised for the search of cosmic neutrinos, this telescope is also sensitive to nuclearites (massive nuggets of strange quark matter [1]) trough the black body radiation emitted along their path [2]. We discuss here the possible detection of non-relativistic down-going nuclearites with the ANTARES telescope and present the results of an analysis using data collected from 2009 till 2017.
CRIS-Team Scopus Importer:2022-12-23

Search for Pre-Burst Emission from Binary Neutron Star Mergers with Spectrum–Roentgen–Gamma - Mereminskiy, I. A.; Lutovinov, A. A.; Postnov, K. A.; Arefiev, V. A.; Lapshov, I. Yu; Molkov, S.; Sazonov, S. Yu; Semena, A. N.; Tkachenko, A. Yu; Shtykovsky, A. E.; Liu, Z.; Wilms, Jörn; et al. (Astronomy Letters-A Journal of Astronomy and Space Astrophysics, 2022)
Abstract: Close binary systems consisting of two neutron stars (BNS) emit gravitational waves, that allow them to merge on timescales shorter than Hubble time. It is widely believed, that NS–NS mergers in such systems power short gamma-ray bursts (GRB). Several mechanisms which could lead to electromagnetic energy release prior to a merger have been proposed. We estimate the ability to observe the possible pre-burst emission with telescopes of Spectrum–Roentgen–Gamma. We also investigate first such event, GRB210919A, which fell into the field of view of the SRG telescopes less than two days before the burst.
CRIS-Team Scopus Importer:2022-11-18
Keywords: gamma-ray burst; surveys; X-ray sources

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search for Strange Quark Matter from the International Space Station with the Mini-EUSO experiment - Casolino, M.; Abe, S.; Adams, J. H.; Allard, D.; Alldredge, P.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Bagheri, M.; Baret, B.; Barghini, D.; Battisti, M.; et al. (Proceedings of Science, 2024)
Mini-EUSO (Multiwavelength Imaging New Instrument for the Extreme Universe Space Observatory) is a telescope observing the Earth from the International Space Station since 2019. The instrument employs a Fresnel-lens optical system and a focal surface composed of 36 Multi-Anode Photomultiplier tubes, 64 channels each, for a total of 2304 channels with single photon counting sensitivity. Mini-EUSO observes the night-time Earth in the near UV range (predominantly between 290 - 430 nm) with a spatial resolution of about 6.3 km (full field of view equal to 44◦) and a temporal resolution of 2.5 μs, observing our planet through a nadir-facing UV-transparent window located in the Russian Zvezda module. The detector can thus acquire triggered transient phenomena with a sampling rate of 2.5 μs and 320 μs, as well as perform continuous acquisition at 40.96 ms scale. Among the scientific objectives addressed by the mission is the observation of meteors (at the 40.96 ms time frame), the search for interstellar meteors and amongst them, the search for strange quark matter (SQM), appearing as anomalous (long track and fast-moving) meteor events. In this paper we discuss the observational capabilities for Mini-EUSO and the limits it will pose to SQM and other Macro-like particles.
CRIS-Team Scopus Importer:2025-02-04

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Sensitivity Modeling for LiteBIRD - Hasebe, T.; Ade, P. A.R.; Adler, A.; Allys, E.; Alonso, D.; Arnold, K.; Auguste, D.; Aumont, J.; Aurlien, R.; Austermann, J.; Azzoni, S.; Baccigalupi, C.; et al. (Journal of Low Temperature Physics, 2022)
LiteBIRD is a future satellite mission designed to observe the polarization of the cosmic microwave background radiation in order to probe the inflationary universe. LiteBIRD is set to observe the sky using three telescopes with transition-edge sensor bolometers. In this work we estimated the LiteBIRD instrumental sensitivity using its current design. We estimated the detector noise due to the optical loadings using physical optics and ray-tracing simulations. The noise terms associated with thermal carrier and readout noise were modeled in the detector noise calculation. We calculated the observational sensitivities over fifteen bands designed for the LiteBIRD telescopes using assumed observation time efficiency.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Astronomy; CMB; Cosmology; Detector noise; Satellite; Sensitivity

Space experiment TUS on board the Lomonosov satellite as pathfinder of JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
Space-based detectors for the study of extreme energy cosmic rays (EECR) are being prepared as a promising new method for detecting highest energy cosmic rays. A pioneering space device - the "tracking ultraviolet set-up" (TUS) - is in the last stage of its construction and testing. The TUS detector will collect preliminary data on EECR in the conditions of a space environment, which will be extremely useful for planning the major JEM-EUSO detector operation.
Keywords: Air-shower fluorescence telescope; JEM-EUSO; Pathfinder

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

SRG/eROSITA status and operations during the first four all-sky surveys - Coutinho, D.; Ramos-Ceja, M. E.; Dennerl, K.; Haberl, F.; Meidinger, N.; Merloni, A.; Predehl, P.; Stewart, I.; Freyberg, M.; Bornemann, W.; Brunner, H.; Burwitz, V.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the soft X-ray scientific payload on board the SRG (Spektrum-Roentgen-Gamma) mission. It was successfully launched from Baikonur in July 2019. Following a 101 days cruise phase, SRG reached its final orbit around the Sun-Earth Lagrangian point L2, from where it has carried out already four full-sky surveys. eROSITA is a complex instrument composed of seven identical co-aligned X-ray telescopes with a focal length of 1600mm and an aperture of 350mm. Each telescope is equipped with an independent CCD camera. The cold redundant ITC (Interface and Thermal Controller) manages all seven cameras as well as the thermal control of the telescope and the interface to the spacecraft. The cruise phase of SRG was used to verify that all systems had survived launch and no degradation in the functionality was present. Following that, the main science mission, comprised of an early Calibration and Performance Verification Phase, followed by the all-sky survey. This paper presents the performance of the eROSITA telescope during the first four complete all-sky surveys. It presents the challenges encountered during the telescope operations as well as the operations and mitigation strategies put in place to understand or minimize the effects of the space environment in L2, such as micrometeoroid hits and radiation damage of the detectors.
CRIS-Team Scopus Importer:2022-11-04
Keywords: all-sky survey; eROSITA; L2; operations; space telescope; Spectrum-Roentgen-Gamma; SRG; X-ray telescope

SRG/eROSITA-triggered XMM-Newton observations of three Be/X-ray binaries in the LMC: Discovery of X-ray pulsations - Haberl, F.; Maitra, C.; Kaltenbrunner, D.; Buckley, D. A.H.; Monageng, I. M.; Udalski, A.; Doroshenko, V.; Ducci, L.; Kreykenbohm, Ingo; Maggi, P.; Rau, A.; Vasilopoulos, G.; et al. (Astronomy & Astrophysics, 2023)
Context. Using data from eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma (SRG), we report the discovery of two new hard transients, eRASSU J050810.4-660653 and eRASSt J044811.1-691318, in the Large Magellanic Cloud. We also report the detection of the Be/X-ray binary RX J0501.6-7034 in a bright state. Aims. We initiated follow-up observations to investigate the nature of the new transients and to search for X-ray pulsations coming from RX J0501.6-7034. Methods. We analysed the X-ray spectra and light curves from our XMM-Newton observations, obtained optical spectra using the South African Large Telescope to look for Balmer emission lines and utilised the archival data from the Optical Gravitational Lensing Experiment (OGLE) for the long-term monitoring of the optical counterparts. Results. We find X-ray pulsations for eRASSU J050810.4-660653, RX J0501.6-7034, and eRASSt J044811.1-691318 of 40.6 s, 17.3 s, and 784 s, respectively. The Hα emission lines with equivalent widths of -10.4 Å (eRASSU J050810.4-660653) and -43.9 Å (eRASSt J044811.1-691318) were measured, characteristic for a circumstellar disc around Be stars. The OGLE I- and V-band light curves of all three systems exhibit strong variability. A regular pattern of deep dips in the light curves of RX J0501.6-7034 suggests an orbital period of ∼451 days. Conclusions. We identify the two new hard eROSITA transients eRASSU J050810.4-660653 and eRASSt J044811.1-691318 and the known Be/X-ray binary RX J0501.6-7034 as Be/X-ray binary pulsars.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Be; Galaxies: individual: LMC; Stars: emission-line; Stars: neutron; X-rays: binaries

Staring at 4U 1909+07 with Suzaku - Fürst, Felix; Pottschmidt, K.; Kreykenbohm, Ingo; Müller, Sebastian; Kühnel, Matthias; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2012)
We present an analysis of the neutron star high mass X-ray binary (HMXB) 4U 1909+07 mainly based on Suzaku data. We extend the pulse period evolution, which behaves in a random-walk like manner, indicative of direct wind accretion. Studying the spectral properties of 4U 1909+07 between 0.5 to 90 keV we find that a power-law with an exponential cutoff can describe the data well, when additionally allowing for a blackbody or a partially covering absorber at low energies.We find no evidence for a cyclotron resonant scattering feature (CRSF), a feature seen in many other neutron star HMXBs sources. By performing pulse phase resolved spectroscopy we investigate the origin of the strong energy dependence of the pulse profile, which evolves from a broad two-peak profile at low energies to a profile with a single, narrow peak at energies above 20 keV. Our data show that it is very likely that a higher folding energy in the high energy peak is responsible for this behavior. This in turn leads to the assumption that we observe the two magnetic poles and their respective accretion columns at different phases, and that these accretion columns have slightly different physical conditions.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

Study of the many fluorescent lines and the absorption variability in GX 301-2 with XMM-Newton - Fürst, Felix; Suchy, S.; Kreykenbohm, Ingo; Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Caballero, I.; Kretschmar, Peter; Ferrigno, Carlo; Rothschild, R. E. (Astronomy & Astrophysics, 2011)
We present an in-depth study of the high mass X-ray binary (HMXB) GX 301-2 during its pre-periastron flare using data from the XMM-Newton satellite. The energy spectrum shows a power law continuum absorbed by a large equivalent hydrogen column on the order of 10(24) cm(-2) and a prominent Fe K alpha fluorescent emission line. Besides the Fe K alpha line, evidence for Fe K beta, Ni K alpha, Ni K beta, S K alpha, Ar K alpha, Ca K alpha, and Cr K alpha fluorescent lines is found. The observed line strengths are consistent with fluorescence in a cold absorber. This is the first time that Cr K alpha is seen in emission in the X-ray spectrum of a HMXB. In addition to the modulation by the strong pulse period of similar to 685 s the source is highly variable and shows different states of activity. We perform time-resolved as well as pulse-to-pulse resolved spectroscopy to investigate differences between these states of activity. We find that fluorescent line fluxes are strongly variable and generally follow the overall flux. The N-H value is variable by a factor of 2, but not correlated to continuum normalization. We find an interval of low flux in the light curve in which the pulsations cease almost completely, without any indication of an increasing absorption column. We investigate this dip in detail and argue that it is most likely that during the dip the accretion ceased and the afterglow of the fluorescent iron accounted for the main portion of the X-ray flux. A similar dip was found earlier in RXTE data, and we compare our findings to these results.
Keywords: stars: neutron; accretion; accretion disks; X-rays: binaries; X-rays: individuals: GX 301-2

Suzaku observation of IGR J16318-4848 - Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Kreykenbohm, Ingo; Walter, R.; Tomsick, J. A. (Astronomy & Astrophysics, 2009)
We report on the first Suzaku observation of IGR J16318-4848, the most extreme example of a new group of highly absorbed X-ray binaries that have recently been discovered by the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The Suzaku observation was carried out between 2006 August 14 and 17, with a net exposure time of 97 ks.The average X-ray spectrum of the source can be well described (chi(2)(red) = 0.99) with a continuum model typical for neutron stars i.e., a strongly absorbed power law continuum with a photon index of 0.676(42) and an exponential cutoff at 20.5(6) keV. The absorbing column is N-H = 1.95(3) x 10(24) cm(-2). Consistent with earlier work, strong fluorescent emission lines of Fe K alpha, Fe K beta, and Ni K alpha are observed. Despite the large N-H, no Compton shoulder is seen in the lines, arguing for a non-spherical and inhomogeneous absorber. Seen at an average 5-60 keV absorbed flux of 3.4x10(-10) erg cm(-2) s(-1), the source exhibits significant variability on timescales of hours.
Keywords: stars: individual IGR J16318-4848; binaries: general; X-rays: binaries

Suzaku observations of the 2013 outburst of KS 1947+300 - Ballhausen, Ralf; Kühnel, Matthias; Pottschmidt, Katja; Furst, Felix; Hemphill, Paul B.; Falkner, Sebastian; Gottlieb, Amy M.; Grinberg, Victoria; Kretschmar, Peter; Kreykenbohm, Ingo; Rothschild, Richard E.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
We report on the timing and spectral analysis of two Suzaku observations with different flux levels of the high-mass X-ray binary KS 1947+300 during its 2013 outburst. In agreement with simultaneous NuSTAR observations, the continuum is well described by an absorbed power law with a cutoff and an additional blackbody component. In addition, we find fluorescent emission from neutral, He-like, and even H-like iron. We determine a pulse period of 18.8 s with the source showing a spin-up between the two observations. Both Suzaku observations show very similar behavior of the pulse profile, which is strongly energy dependent. This profile has an evolution from a profile with one peak at low energies to a profile with two peaks of different widths toward higher energies seen in both the Suzaku and NuSTAR data. Such an evolution to a more complex profile at higher energies is rarely seen in X-ray pulsars, most cases show the opposite behavior. Pulse phase-resolved spectral analysis shows a variation in the absorbing column density, N, over pulse phase. Spectra taken during the pulse profile minima are intrinsically softer compared to the pulse phase-averaged spectrum.
Keywords: Accretion; accretion disks; Pulsars: individual: KS 1947+300; X-rays: binaries

SUZAKU OBSERVATIONS OF THE HMXB 1A 1118-61 - Suchy, Slawomir; Pottschmidt, Katja; Rothschild, Richard E.; Wilms, Jörn; Fürst, Felix; Barragan, Laura; Caballero, Isabel; Grinberg, Victoria; Kreykenbohm, Ingo; Doroshenko, Victor; Santangelo, Andrea; Staubert, Ruediger; et al. (Astrophysical Journal, 2011)
We present broadband analysis of the Be/X-ray transient 1A 1118-61 by Suzaku at the peak of its third observed outburst in 2009 January and two weeks later when the source flux had decayed by an order of magnitude. The continuum was modeled with a cutoffpl model as well as a compTT model, with both cases requiring an additional blackbody component at lower energies. We confirm the detection of a cyclotron line at similar to 55 keV and discuss the possibility of a first harmonic at similar to 110 keV. Pulse profile comparisons show a change in the profile structure at lower energies, an indication for possible changes in the accretion geometry. Phase-resolved spectroscopy in the outburst data shows a change in the continuum throughout the pulse period. The decrease in the cyclotron resonance scattering feature centroid energy also indicates that the viewing angle on the accretion column is changing throughout the pulse period.
Keywords: pulsars: individual (1A 1118-61); stars: magnetic field; X-rays: binaries; X-rays: stars

Synthetic simulations of the extragalactic sky seen by eROSITA I. Pre-launch selection functions from Monte-Carlo simulations - Clerc, N.; Ramos-Ceja, M. E.; Ridl, J.; Lamer, G.; Brunner, H.; Hofmann, Florian; Comparat, J.; Pacaud, Florian; Kaefer, F.; Reiprich, T. H.; Merloni, A.; Schmid, Christian; et al. (Astronomy & Astrophysics, 2018)
Context. Studies of galaxy clusters provide stringent constraints on models of structure formation. Provided that selection effects are under control, large X-ray surveys are well suited to derive cosmological parameters, in particular those governing the dark energy equation of state.Aims. We forecast the capabilities of the all-sky eROSITA (extended ROentgen Survey with an Imaging Telescope Array) survey to be achieved by the early 2020s. We bring special attention to modelling the entire chain from photon emission to source detection and cataloguing.Methods. The selection function of galaxy clusters for the upcoming eROSITA mission is investigated by means of extensive and dedicated Monte-Carlo simulations. Employing a combination of accurate instrument characterisation and a state-of-the-art source detection technique, we determine a cluster detection efficiency based on the cluster fluxes and sizes.Results. Using this eROSITA cluster selection function, we find that eROSITA will detect a total of approximately 10(5) clusters in the extra-galactic sky. This number of clusters will allow eROSITA to put stringent constraints on cosmological models. We show that incomplete assumptions on selection effects, such as neglecting the distribution of cluster sizes, induce a bias in the derived value of cosmological parameters.Conclusions. Synthetic simulations of the eROSITA sky capture the essential characteristics impacting the next-generation galaxy cluster surveys and they highlight parameters requiring tight monitoring in order to avoid biases in cosmological analyses.
Keywords: cosmological parameters; surveys; large-scale structure of Universe; X-rays: galaxies: clusters; cosmology: observations; methods: data analysis

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

The accretion environment in Vela X-1 during a flaring period using XMM-Newton - Martinez-Nunez, Silvia; Torrejon, J. M.; Kühnel, Matthias; Kretschmar, Peter; Stuhlinger, M.; Rodes-Roca, J. J.; Fuerst, F.; Kreykenbohm, Ingo; Martin-Carrillo, A.; Pollock, A. M. T.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
We present analysis of 100 ks contiguous XMM-Newton data of the prototypical wind accretor Vela X-1. The observation covered eclipse egress between orbital phases 0.134 and 0.265, during which a giant flare took place, enabling us to study the spectral properties both outside and during the flare. This giant flare with a peak luminosity of 3.92(-0.09)(+0.42) x 10(37) erg s(-1) allows estimates of the physical parameters of the accreted structure with a mass of similar to 10(21) g. We have been able to model several contributions to the observed spectrum with a phenomenological model formed by three absorbed power laws plus three emission lines. After analysing the variations with orbital phase of the column density of each component, as well as those in the Fe and Ni fluorescence lines, we provide a physical interpretation for each spectral component. Meanwhile, the first two components are two aspects of the principal accretion component from the surface of the neutron star, the third component seems to be the X-ray light echo formed in the stellar wind of the companion.
Keywords: X-rays: binaries; pulsars: individual: Vela X-1

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The Athena X-ray Integral Field Unit: a consolidated design for the system requirement review of the preliminary definition phase - Barret, Didier; Albouys, Vincent; Den Herder, Jan-Willem; Piro, Luigi; Cappi, Massimo; Huovelin, Juhani; Kelley, Richard; Miguel Mas-Hesse, J.; Paltani, Stephane; Rauw, Gregor; Rozanska, Agata; Svoboda, Jiri; et al. (Experimental Astronomy, 2023)
The Athena X-ray Integral Unit (X-IFU) is the high resolution X-ray spectrometer studied since 2015 for flying in the mid-30s on the Athena space X-ray Observatory. Athena is a versatile observatory designed to address the Hot and Energetic Universe science theme, as selected in November 2013 by the Survey Science Committee. Based on a large format array of Transition Edge Sensors (TES), X-IFU aims to provide spatially resolved X-ray spectroscopy, with a spectral resolution of 2.5 eV (up to 7 keV) over a hexagonal field of view of 5 arc minutes (equivalent diameter). The X-IFU entered its System Requirement Review (SRR) in June 2022, at about the same time when ESA called for an overall X-IFU redesign (including the X-IFU cryostat and the cooling chain), due to an unanticipated cost overrun of Athena. In this paper, after illustrating the breakthrough capabilities of the X-IFU, we describe the instrument as presented at its SRR (i.e. in the course of its preliminary definition phase, so-called B1), browsing through all the subsystems and associated requirements. We then show the instrument budgets, with a particular emphasis on the anticipated budgets of some of its key performance parameters, such as the instrument efficiency, spectral resolution, energy scale knowledge, count rate capability, non X-ray background and target of opportunity efficiency. Finally, we briefly discuss the ongoing key technology demonstration activities, the calibration and the activities foreseen in the X-IFU Instrument Science Center, touch on communication and outreach activities, the consortium organisation and the life cycle assessment of X-IFU aiming at minimising the environmental footprint, associated with the development of the instrument. Thanks to the studies conducted so far on X-IFU, it is expected that along the design-to-cost exercise requested by ESA, the X-IFU will maintain flagship capabilities in spatially resolved high resolution X-ray spectroscopy, enabling most of the original X-IFU related scientific objectives of the Athena mission to be retained. The X-IFU will be provided by an international consortium led by France, The Netherlands and Italy, with ESA member state contributions from Belgium, Czech Republic, Finland, Germany, Poland, Spain, Switzerland, with additional contributions from the United States and Japan.
CRIS-Team WoS Importer:2023-03-17

The atmospheric monitoring system of the JEM-EUSO instrument - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will detect Ultra-High Energy Cosmic Rays (UHECRs) from space, detecting the UV Fluorescence Light produced by Extensive Air Showers (EAS) induced by the interaction of the cosmic rays with the earth's atmosphere. The capability to reconstruct the properties of the primary cosmic ray depends on the accurate measurement of the atmospheric conditions in the region of EAS development. The Atmospheric Monitoring (AM) system of JEM-EUSO will host a LIDAR, operating in the UV band, and an Infrared camera to monitor the cloud cover in the JEM-EUSO Field of View, in order to be sensitive to clouds with an optical depth tau a parts per thousand yen 0.15 and to measure the cloud top altitude with an accuracy of 500 m and an altitude resolution of 500 m.
Keywords: Ultra high energy cosmic rays; Atmospheric monitoring; IR camera; LIDAR

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The enhanced X-ray Timing and Polarimetry mission – eXTP: an update on its scientific cases, mission profile and development status - Zhang, Shuang Nan; Santangelo, Andrea; Xu, Yupeng; Feroci, Marco; Hernanz, Margarita; Lu, Fangjun; Chen, Yong; Feng, Hua; Nandra, Kirpal; Jiang, Weichun; Svoboda, Jiri; Brandt, Søren; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
The enhanced X-ray Timing and Polarimetry mission (eXTP) is a flagship observatory for X-ray timing, spectroscopy and polarimetry developed by an International Consortium. Thanks to its very large collecting area, good spectral resolution and unprecedented polarimetry capabilities, eXTP will explore the properties of matter and the propagation of light in the most extreme conditions found in the Universe. eXTP will, in addition, be a powerful X-ray observatory. The mission will continuously monitor the X-ray sky, and will enable multiwavelength and multi-messenger studies. The mission is currently in phase B, which will be completed in the middle of 2022.
CRIS-Team Scopus Importer:2022-11-04
Keywords: black hole; equation of state; extreme density; extreme gravity; extreme magnetism; neutron star; X-ray polarimetry; X-ray timing

The enhanced X-ray Timing and Polarimetry mission-eXTP - Zhang, Shuangnan; Santangelo, Andrea; Feroci, Marco; Xu, Yupeng; Lu, Fangjun; Chen, Yong; Feng, Hua; Zhang, Shu; Brandt, Soren; Hernanz, Margarita; Baldini, Luca; Bozzo, Enrico; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this paper we present the enhanced X-ray Timing and Polarimetry mission-eXTP. eXTP is a space science mission designed to study fundamental physics under extreme conditions of density, gravity and magnetism. The mission aims at determining the equation of state of matter at supra-nuclear density, measuring effects of QED, and understanding the dynamics of matter in strong-field gravity. In addition to investigating fundamental physics, eXTP will be a very powerful observatory for astrophysics that will provide observations of unprecedented quality on a variety of galactic and extragalactic objects. In particular, its wide field monitoring capabilities will be highly instrumental to detect the electro-magnetic counterparts of gravitational wave sources. The paper provides a detailed description of: (1) the technological and technical aspects, and the expected performance of the instruments of the scientific payload; (2) the elements and functions of the mission, from the spacecraft to the ground segment.
CRIS-Team WoS Importer:2019-03-08

The eROSITA Final Equatorial Depth Survey (eFEDS): X-ray catalogue - Brunner, H.; Liu, T.; Lamer, G.; Georgakakis, A.; Merloni, A.; Brusa, M.; Bulbul, E.; Dennerl, K.; Friedrich, S.; Liu, A.; Maitra, C.; Nandra, K.; et al. (Astronomy & Astrophysics, 2022)
Context. The eROSITA X-ray telescope on board the Spectrum-Poentgen-Gamma (SPG) observatory combines a large field of view and a large collecting area in the energy range between 0.2 and 8.0 keV. This gives the telescope the capability to perform uniform scanning observations of large sky areas. Aims. SRG/eROSITA performed scanning observations of the 140 square degree eROSITA Final Equatorial Depth Survey field (the eFEDS field) as part of its performance verification phase ahead of the planned four year of all-sky scanning operations. The observing time of eFEDS was chosen to slightly exceed the depth expected in an equatorial field after the completion of the all-sky survey. While verifying the capability of eROSITA to perform large-area uniform surveys and saving as a test and training dataset to establish calibration and data analysis procedures, the eFEDS survey also constitutes the largest contiguous soft X-ray survey at this depth to date, supporting a range of early eROSITA survey science investigations. Here we (i) present a catalogue of detected X-ray sources in the eFEDS field providing information about source positions and extent, as well as fluxes in multiple energy bands, and (ii) document the suite of tools and procedures developed for eROSITA data processing and analysis, which were validated and optimised by the eFEDS work. Methods. The data were fed through a standard data processing pipeline, which appltes X-ray event calibration and provides a set of standard calibrated data products. A mutiti-stage source detection procedure, building in part on experience from XMM-Newton, was optimised and calibrated by performing realistic simulations of the eROSITA eFEDS observations. Source fluxes were computed in multiple standard energy bands by forced point source fitting and aperture photometry. We cross-matched the eROSITA eFEDS source catalogue with previous XMM-ATLAS observations, which confirmed the excellentt agreement of the eROSITA and XMM-ATLAS source fluxes. Astrometric corrections were performed by cross-matching the eROSITA source positions with an optical reference catalogue of quasars. Results. We present a primary catalogue of 27 910 X-ray sources (542 of which are significantly spatially extended) detected in the 0.2-2.3 keV energy range with detection likelihoods ≥6, corresponding to a (point source) flux limit of 6.5 × 10-15 erg cm-2 s-1 in the 0.5-2.0 keV energy band (80% completeness). A supplementary catalogue contains 4774 low-significance source candidates with detection likelihoods between 5 and 6. In addition, a hard-band sample of 246 sources detected in the energy range 22.3-5.0 keV above a detection likelihood of 10 is provided. In an appendix, we finally describe the dedicated data analysis software package, the eROSITA calibration database, and the standard calibrated data products.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Catalogs; Surveys; X-rays: general

The eROSITA X-ray telescope on SRG - Predehl, P.; Andritschke, R.; Arefiev, V.; Babyshkin, V.; Batanov, O.; Becker, W.; Böhringer, H.; Bogomolov, A.; Boller, T.; Borm, K.; Bornemann, W.; Bräuninger, H.; et al. (Astronomy & Astrophysics, 2021)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on the Spectrum-Roentgen-Gamma (SRG) mission, which was successfully launched on July 13, 2019, from the Baikonour cosmodrome. After the commissioning of the instrument and a subsequent calibration and performance verification phase, eROSITA started a survey of the entire sky on December 13, 2019. By the end of 2023, eight complete scans of the celestial sphere will have been performed, each lasting six months. At the end of this program, the eROSITA all-sky survey in the soft X-ray band (0.2-2.3 keV) will be about 25 times more sensitive than the ROSAT All-Sky Survey, while in the hard band (2.3-8 keV) it will provide the first ever true imaging survey of the sky. The eROSITA design driving science is the detection of large samples of galaxy clusters up to redshifts z > 1 in order to study the large-scale structure of the universe and test cosmological models including Dark Energy. In addition, eROSITA is expected to yield a sample of a few million AGNs, including obscured objects, revolutionizing our view of the evolution of supermassive black holes. The survey will also provide new insights into a wide range of astrophysical phenomena, including X-ray binaries, active stars, and diffuse emission within the Galaxy. Results from early observations, some of which are presented here, confirm that the performance of the instrument is able to fulfil its scientific promise. With this paper, we aim to give a concise description of the instrument, its performance as measured on ground, its operation in space, and also the first results from in-orbit measurements.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dark energy; Space vehicles: instruments; Surveys; X-rays: general

The EUSO-Balloon pathfinder - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Barrillon, P.; Batsch, T.; et al. (Experimental Astronomy, 2015)
EUSO-Balloon is a pathfinder for JEM-EUSO, the Extreme Universe Space Observatory which is to be hosted on-board the International Space Station. As JEM-EUSO is designed to observe Ultra-High Energy Cosmic Rays (UHECR)-induced Extensive Air Showers (EAS) by detecting their ultraviolet light tracks "from above", EUSO-Balloon is a nadir-pointing UV telescope too. With its Fresnel Optics and Photo-Detector Module, the instrument monitors a 50 km(2) ground surface area in a wavelength band of 290-430 nm, collecting series of images at a rate of 400,000 frames/sec. The objectives of the balloon demonstrator are threefold: a) perform a full end-to-end test of a JEM-EUSO prototype consisting of all the main subsystems of the space experiment, b) measure the effective terrestrial UV background, with a spatial and temporal resolution relevant for JEM-EUSO. c) detect tracks of ultraviolet light from near space for the first time. The latter is a milestone in the development of UHECR science, paving the way for any future space-based UHECR observatory. On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. From a float altitude of 38 km, the instrument operated during the entire astronomical night, observing UV-light from a variety of ground-covers and from hundreds of simulated EASs, produced by flashers and a laser during a two-hour helicopter under-flight.
Keywords: UHECR; Air-fluorescence; JEM-EUSO; Balloon experiment

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The giant outburst of 4U 0115+634 in 2011 with Suzaku and RXTE: Minimizing cyclotron line biases - Kühnel, Matthias; Kreykenbohm, Ingo; Ferrigno, Carlo; Pottschmidt, Katja; Marcu-Cheatham, Diana M.; Fuerst, Felix; Rothschild, Richard E.; Kretschmar, Peter; Klochkov, Dmitry; Hemphill, Paul; Hertel, Dominik; Müller, Sebastian; et al. (Astronomy & Astrophysics, 2020)
We present an analysis of X-ray spectra of the high-mass X-ray binary 4U 0115+634 as observed with Suzaku and RXTE in 2011 July, during the fading phase of a giant X-ray outburst. We used a continuum model consisting of an absorbed cutoff power law and an ad hoc Gaussian emission feature centered around 8.5 keV, which we attribute to cyclotron emission. Our results are consistent with a fundamental cyclotron absorption line centered at similar to 10.2 keV for all observed flux ranges. At the same time we rule out significant influence of the 8.5 kev Gaussian on the parameters of the cyclotron resonant scattering feature, which are not consistent with the cyclotron line energies or the depths of previously reported flux-dependent descriptions. We also show that some continuum models can lead to artificial line-like residuals in the analyzed spectra, which are then misinterpreted as unphysically strong cyclotron lines. Specifically, our results do not support the existence of a previously claimed additional cyclotron feature at similar to 15 keV. Apart from these features, we find for the first time evidence for a He-like FeXXV emission line at similar to 6.7 keV and weak H-like FeXXVI emission close to similar to 7.0 keV.
CRIS-Team WoS Importer:2020-03-13

The goodness of simultaneous fits in ISIS - Kühnel, Matthias; Falkner, Sebastian; Großberger, Christoph; Ballhausen, Ralf; Dauser, Thomas; Schwarm, Fritz-Walter; Kreykenbohm, Ingo; Nowak, Michael A.; Pottschmidt, Katja; Ferrigno, Carlo; Rothschild, Richard E.; Martínez-Núñez, Silvia; et al. (Acta Polytechnica, 2016)
In a previous work, we introduced a tool for analyzing multiple datasets simultaneously, which has been implemented into ISIS. This tool was used to fit many spectra of X-ray binaries. However, the large number of degrees of freedom and individual datasets raise an issue about a good measure for a simultaneous fit quality. We present three ways to check the goodness of these fits: we investigate the goodness of each fit in all datasets, we define a combined goodness exploiting the logical structure of a simultaneous fit, and we stack the fit residuals of all datasets to detect weak features. These tools are applied to all RXTE-spectra from GRO 1008−57, revealing calibration features that are not detected significantly in any single spectrum. Stacking the residuals from the best-fit model for the Vela X-1 and XTE J1859+083 data evidences fluorescent emission lines that would have gone undetected otherwise.
Keywords: Data analysis; Multiple datasets; X-rays binaries

The infrared camera onboard JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on the Japanese Experiment Module (JEM-EUSO) on board the International Space Station (ISS) is the first space-based mission worldwide in the field of Ultra High-Energy Cosmic Rays (UHECR). For UHECR experiments, the atmosphere is not only the showering calorimeter for the primary cosmic rays, it is an essential part of the readout system, as well. Moreover, the atmosphere must be calibrated and has to be considered as input for the analysis of the fluorescence signals. Therefore, the JEM-EUSO Space Observatory is implementing an Atmospheric Monitoring System (AMS) that will include an IR-Camera and a LIDAR. The AMS Infrared Camera is an infrared, wide FoV, imaging system designed to provide the cloud coverage along the JEM-EUSO track and the cloud top height to properly achieve the UHECR reconstruction in cloudy conditions. In this paper, an updated preliminary design status, the results from the calibration tests of the first prototype, the simulation of the instrument, and preliminary cloud top height retrieval algorithms are presented.
Keywords: JEM-EUSO; Space observatory; IR-camera; Ultra-High Energy Cosmic Rays (UHECR)

The JEM-EUSO mission: An introduction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Pernas, M. Ave; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on board the Japanese Experiment Module of the International Space Station, JEM-EUSO, is being designed to search from space ultra-high energy cosmic rays. These are charged particles with energies from a few 10(19) eV to beyond 10(20) eV, at the very end of the known cosmic ray energy spectrum. JEM-EUSO will also search for extreme energy neutrinos, photons, and exotic particles, providing a unique opportunity to explore largely unknown phenomena in our Universe. The mission, principally based on a wide field of view (60 degrees) near-UV telescope with a diameter of similar to 2.5 m, will monitor the earth's atmosphere at night, pioneering the observation from space of the ultraviolet tracks (290-430 nm) associated with giant extensive air showers produced by ultra-high energy primaries propagating in the earth's atmosphere. Observing from an orbital altitude of similar to 400 km, the mission is expected to reach an instantaneous geometrical aperture of A (g e o) a parts per thousand yen 2 x 10(5) km(2) sr with an estimated duty cycle of similar to 20 %. Such a geometrical aperture allows unprecedented exposures, significantly larger than can be obtained with ground-based experiments. In this paper we briefly review the history of space-based search for ultra-high energy cosmic rays. We then introduce the special issue of Experimental Astronomy devoted to the various aspects of such a challenging enterprise. We also summarise the activities of the on-going JEM-EUSO program.
Keywords: Ultra-high energy cosmic rays; Neutrinos

The JEM-EUSO observation in cloudy conditions - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO (Extreme Universe Space Observatory on-board the Japanese Experiment Module) mission will conduct extensive air shower (EAS) observations on the International Space Station (ISS). Following the ISS orbit, JEM-EUSO will experience continuous changes in the atmospheric conditions, including cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate from both EAS property and cloud climatology points of view. In the present work, the impact of clouds on the apparent profile of EAS is demonstrated through the simulation studies, taking into account the JEM-EUSO instrument and properties of the clouds. These results show a dependence on the cloud-top altitude and optical depth of the cloud. The analyses of satellite measurements on the cloud distribution indicate that more than 60 % of the cases allow for conventional EAS observation, and an additional similar to 20 % with reduced quality. The combination of the relevant factors results in an effective trigger aperture of EAS observation similar to 72 %, compared to the one in the clear atmosphere condition.
Keywords: JEM-EUSO; Ultra-high energy cosmic ray; Extensive air shower

The Large Observatory For x-ray Timing - Feroci, Marco; Den Herder, J. W.; Bozzo, E.; Barret, D.; Brandt, Soren; Hernanz, Margarita; Van Der Klis, M.; Pohl, M.; Santangelo, A.; Stella, L.; Watts, A.; Wilms, Jörn; et al. (2014)
The Large Observatory For x-ray Timing (LOFT) was studied within ESA M3 Cosmic Vision framework and participated in the final downselection for a launch slot in 2022-2024. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument, LOFT will study the behaviour of matter under extreme conditions, such as the strong gravitational field in the innermost regions of accretion flows close to black holes and neutron stars, and the supranuclear densities in the interior of neutron stars. The science payload is based on a Large Area Detector (LAD, 10 m(2) effective area, 2-30 keV, 240 eV spectral resolution, 1 degrees collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g. GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the status of the mission at the end of its Phase A study.
Keywords: X-ray timing; X-ray spectroscopy; X-ray imaging; compact objects; X-ray detectors; microchannel plates

The Large Observatory for X-ray Timing (LOFT) - Feroci, Marco; Stella, L.; Van Der Klis, M.; Courvoisier, T. J. -L.; Hernanz, Margarita; Hudec, R.; Santangelo, A.; Walton, D.; Zdziarski, A.; Barret, D.; Belloni, T.; Braga, J.; et al. (Experimental Astronomy, 2012)
High-time-resolution X-ray observations of compact objects provide direct access to strong-field gravity, to the equation of state of ultradense matter and to black hole masses and spins. A 10 m(2)-class instrument in combination with good spectral resolution is required to exploit the relevant diagnostics and answer two of the fundamental questions of the European Space Agency (ESA) Cosmic Vision Theme "Matter under extreme conditions", namely: does matter orbiting close to the event horizon follow the predictions of general relativity? What is the equation of state of matter in neutron stars? The Large Observatory For X-ray Timing (LOFT), selected by ESA as one of the four Cosmic Vision M3 candidate missions to undergo an assessment phase, will revolutionise the study of collapsed objects in our galaxy and of the brightest supermassive black holes in active galactic nuclei. Thanks to an innovative design and the development of large-area monolithic silicon drift detectors, the Large Area Detector (LAD) on board LOFT will achieve an effective area of similar to 12 m(2) (more than an order of magnitude larger than any spaceborne predecessor) in the 2-30 keV range (up to 50 keV in expanded mode), yet still fits a conventional platform and small/medium-class launcher. With this large area and a spectral resolution of < 260 eV, LOFT will yield unprecedented information on strongly curved spacetimes and matter under extreme conditions of pressure and magnetic field strength.
Keywords: Missions; X-ray timing; compact objects; black holes; neutron stars

The LOFT mission concept: A status update - Feroci, M.; Bozzo, E.; Brandt, S.; Hernanz, M.; Van Der Klis, M.; Liu, L. P.; Orleanski, P.; Pohl, M.; Santangelo, A.; Schanne, S.; Stella, L.; Takahashi, T.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Large Observatory For x-ray Timing (LOFT) is a mission concept which was proposed to ESA as M3 and M4 candidate in the framework of the Cosmic Vision 2015-2025 program. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument and the uniquely large field of view of its wide field monitor, LOFT will be able to study the behaviour of matter in extreme conditions such as the strong gravitational field in the innermost regions close to black holes and neutron stars and the supra-nuclear densities in the interiors of neutron stars. The science payload is based on a Large Area Detector (LAD, >8m effective area, 2-30 keV, 240 eV spectral resolution, 1 degree collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g., GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the current technical and programmatic status of the mission.
Keywords: Silicon detectors; spectroscopy; timing; X-ray astronomy

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

The reawakening of the sleeping X-ray pulsar XTE J1946+274 - Müller, Sebastian; Kühnel, Matthias; Caballero, I.; Pottschmidt, K.; Fürst, Felix; Kreykenbohm, Ingo; Sagredo, Macarena; Obst, M.; Wilms, Jörn; Ferrigno, C.; Rothschild, R. E.; Staubert, R. (Astronomy & Astrophysics, 2012)
We report on a series of outbursts of the high-mass X-ray binary XTE J1946+274 in 2010/2011 observed with INTEGRAL, RXTE, and Swift. We discuss possible mechanisms resulting in the extraordinary outburst behavior of this source. The X-ray spectra can be described by standard phenomenological models, enhanced by an absorption feature of unknown origin at about 10 keV and a narrow iron K alpha fluorescence line at 6.4 keV, which are variable in flux and pulse phase. We find possible evidence for a cyclotron resonance scattering feature at about 25 keV at the 93% level. The presence of a strong cyclotron line at 35 keV seen in data from the source's 1998 outburst that was confirmed by a reanalysis of these data can be excluded. This result indicates that the cyclotron line feature in XTE J1946+274 is variable between individual outbursts.
Keywords: X-rays: binaries; accretion; accretion disks

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

The TANAMI Multiwavelength Program: Dynamic spectral energy distributions of southern blazars - Krauß, Felicia; Wilms, Jörn; Kadler, Matthias; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Stevens, J.; Ros, Eduardo; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
Context. Simultaneous broadband spectral and temporal studies of blazars are an important tool for investigating active galactic nuclei (AGN) jet physics. Aims. We study the spectral evolution between quiescent and flaring periods of 22 radio-loud AGN through multiepoch, quasi-simultaneous broadband spectra. For many of these sources these are the first broadband studies. Methods. We use a Bayesian block analysis of Fermi/LAT light curves to determine time ranges of constant flux for constructing quasi-simultaneous spectral energy distributions (SEDs). The shapes of the resulting 81 SEDs are described by two logarithmic parabolas and a blackbody spectrum where needed. Results. The peak frequencies and luminosities agree well with the blazar sequence for low states with higher luminosity implying lower peak frequencies. This is not true for sources in high states. The γ-ray photon index in Fermi/LAT correlates with the synchrotron peak frequency in low and intermediate states. No correlation is present in high states. The black hole mass cannot be determined from the SEDs. Surprisingly, the thermal excess often found in FSRQs at optical/UV wavelengths can be described by blackbody emission and not an accretion disk spectrum. Conclusions. The so-called harder-when-brighter trend, typically seen in X-ray spectra of flaring blazars, is visible in the blazar sequence. Our results for low and intermediate states, as well as the Compton dominance, are in agreement with previous results. Black hole mass estimates using recently published parameters are in agreement with some of the more direct measurements. For two sources, estimates disagree by more than four orders of magnitude, possibly owing to boosting effects. The shapes of the thermal excess seen predominantly in flat spectrum radio quasars are inconsistent with a direct accretion disk origin.
Keywords: BL Lacertae objects: general; Galaxies: active; Quasars: general; Relativistic processes

THE TRANSIENT ACCRETING X-RAY PULSAR XTE J1946+274: STABILITY OF X-RAY PROPERTIES AT LOW FLUX AND UPDATED ORBITAL SOLUTION - Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Kühnel, Matthias; Müller, Sebastian; Falkner, Sebastian; Caballero, Isabel; Finger, Mark H.; Jenke, Peter J.; Wilson-Hodge, Colleen A.; Fuerst, Felix; Grinberg, Victoria; Hemphill, Paul B.; et al. (Astrophysical Journal, 2015)
We present a timing and spectral analysis of the X-ray pulsar XTE J1946+274 observed with Suzaku during an outburst decline in 2010 October and compare with previous results. XTE J1946+274 is a transient X-ray binary consisting of a Be-type star and a neutron star with a 15.75 s pulse period in a 172 days orbit with 2-3 outbursts per orbit during phases of activity. We improve the orbital solution using data from multiple instruments. The X-ray spectrum can be described by an absorbed Fermi-Dirac cut-off power-law model along with a narrow Fe K alpha line at 6.4 keV and a weak Cyclotron Resonance Scattering Feature (CRSF) at similar to 35 keV. The Suzaku data are consistent with the previously observed continuum flux versus iron line flux correlation expected from fluorescence emission along the line of sight. However, the observed iron line flux is slightly higher, indicating the possibility of a higher iron abundance or the presence of non-uniform material. We argue that the source most likely has only been observed in the subcritical (non-radiation dominated) state since its pulse profile is stable over all observed luminosities and the energy of the CRSF is approximately the same at the highest (similar to 5 x 10(37) erg s(-1)) and lowest (similar to 5. x 10(36) erg s(-1)) observed 3-60 keV luminosities.
Keywords: accretion; accretion disks; pulsars: individual (XTE J1946+274); X-rays: binaries

The X-ray Integral Field Unit at the end of the Athena reformulation phase - Peille, Philippe; Barret, Didier; Cucchetti, Edoardo; Albouys, Vincent; Piro, Luigi; Simionescu, Aurora; Cappi, Massimo; Bellouard, Elise; Cénac-Morthé, Céline; Daniel, Christophe; Pradines, Alice; Finoguenov, Alexis; et al. (Experimental Astronomy, 2025)
The Athena mission entered a redefinition phase in July 2022, driven by the imperative to reduce the mission cost at completion for the European Space Agency below an acceptable target, while maintaining the flagship nature of its science return. This notably called for a complete redesign of the X-ray Integral Field Unit (X-IFU) cryogenic architecture towards a simpler active cooling chain. Passive cooling via successive radiative panels at spacecraft level is now used to provide a 50 K thermal environment to an X-IFU owned cryostat. 4.5 K cooling is achieved via a single remote active cryocooler unit, while a multi-stage Adiabatic Demagnetization Refrigerator ensures heat lift down to the 50 mK required by the detectors. Amidst these changes, the core concept of the readout chain remains robust, employing Transition Edge Sensor microcalorimeters and a SQUID-based Time-Division Multiplexing scheme. Noteworthy is the introduction of a slower pixel. This enables an increase in the multiplexing factor (from 34 to 48) without compromising the instrument energy resolution, hence keeping significant system margins to the new 4 eV resolution requirement. This allows reducing the number of channels by more than a factor two, and thus the resource demands on the system, while keeping a 4’ field of view (compared to 5’ before). In this article, we will give an overview of this new architecture, before detailing its anticipated performances. Finally, we will present the new X-IFU schedule, with its short term focus on demonstration activities towards a mission adoption in early 2027
CRIS-Team Scopus Importer:2025-03-21
Keywords: Athena; Instrumentation; Micro-calorimeters; X-ray integral field unit; X-rays

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Towards a Unified View of Inhomogeneous Stellar Winds in Isolated Supergiant Stars and Supergiant High Mass X-Ray Binaries - Martinez-Nunez, Silvia; Kretschmar, Peter; Bozzo, Enrico; Oskinova, Lidia M.; Puls, Joachim; Sidoli, Lara; Sundqvist, Jon Olof; Blay, Pere; Falanga, Maurizio; Furst, Felix; Gimenez-Garcia, Angel; Kreykenbohm, Ingo; et al. (Space Science Reviews, 2017)
Massive stars, at least similar to 10 times more massive than the Sun, have two key properties that make them the main drivers of evolution of star clusters, galaxies, and the Universe as a whole. On the one hand, the outer layers of massive stars are so hot that they produce most of the ionizing ultraviolet radiation of galaxies; in fact, the first massive stars helped to re-ionize the Universe after its Dark Ages. Another important property of massive stars are the strong stellar winds and outflows they produce. This mass loss, and finally the explosion of a massive star as a supernova or a gamma-ray burst, provide a significant input of mechanical and radiative energy into the interstellar space. These two properties together make massive stars one of the most important cosmic engines: they trigger the star formation and enrich the interstellar medium with heavy elements, that ultimately leads to formation of Earth-like rocky planets and the development of complex life. The study of massive star winds is thus a truly multidisciplinary field and has a wide impact on different areas of astronomy.In recent years observational and theoretical evidences have been growing that these winds are not smooth and homogeneous as previously assumed, but rather populated by dense "clumps". The presence of these structures dramatically affects the mass loss rates derived from the study of stellar winds. Clump properties in isolated stars are nowadays inferred mostly through indirect methods (i.e., spectroscopic observations of line profiles in various wavelength regimes, and their analysis based on tailored, inhomogeneous wind models). The limited characterization of the clump physical properties (mass, size) obtained so far have led to large uncertainties in the mass loss rates from massive stars. Such uncertainties limit our understanding of the role of massive star winds in galactic and cosmic evolution.Supergiant high mass X-ray binaries (SgXBs) are among the brightest X-ray sources in the sky. A large number of them consist of a neutron star accreting from the wind of a massive companion and producing a powerful X-ray source. The characteristics of the stellar wind together with the complex interactions between the compact object and the donor star determine the observed X-ray output from all these systems. Consequently, the use of SgXBs for studies of massive stars is only possible when the physics of the stellar winds, the compact objects, and accretion mechanisms are combined together and confronted with observations.This detailed review summarises the current knowledge on the theory and observations of winds from massive stars, as well as on observations and accretion processes in wind-fed high mass X-ray binaries. The aim is to combine in the near future all available theoretical diagnostics and observational measurements to achieve a unified picture of massive star winds in isolated objects and in binary systems.
Keywords: Massive stars; Stellar outflows; X-ray binary; Wind-fed systems; Accretion processes; SgXBs; SFXTs

Towards observations of nuclearites in Mini-EUSO - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
Mini-EUSO is a small orbital telescope with a field of view of 44◦ × 44◦, observing the night-time Earth mostly in 320-420 nm band. Its time resolution spanning from microseconds (triggered) to milliseconds (untriggered) and more than 300 × 300 km of the ground covered, already allowed it to register thousands of meteors. Such detections make the telescope a suitable tool in the search for hypothetical heavy compact objects, which would leave trails of light in the atmosphere due to their high density and speed. The most prominent example are the nuclearites – hypothetical lumps of strange quark matter that could be stabler and denser than the nuclear matter. In this paper, we show potential limits on the flux of nuclearites after collecting 42 hours of observations data.
CRIS-Team Scopus Importer:2024-12-16

Ultra high energy photons and neutrinos with JEM-EUSO (vol 40, pg 215, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Ultra-violet imaging of the night-time earth by EUSO-Balloon towards space-based ultra-high energy cosmic ray observations - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2019)
The JEM-EUSO (Joint Experiment Missions for the Extreme Universe Space Observatory) program aims at developing Ultra-Violet (UV) fluorescence telescopes for efficient detections of Extensive Air Showers (EASs) induced by Ultra-High Energy Cosmic Rays (UHECRs) from satellite orbit. In order to demonstrate key technologies for JEM-EUSO, we constructed the EUSO-Balloon instrument that consists of a ∼1 m 2 refractive telescope with two Fresnel lenses and an array of multi-anode photo-multiplier tubes at the focus. Distinguishing it from the former balloon-borne experiments, EUSO-Balloon has the capabilities of single photon counting with a gate time of 2.3 µs and of imaging with a total of 2304 pixels. As a pathfinder mission, the instrument was launched for an 8 h stratospheric flight on a moonless night in August 2014 over Timmins, Canada. In this work, we analyze the count rates over ∼2.5 h intervals. The measurements are of diffuse light, e.g. of airglow emission, back-scattered from the Earth's atmosphere as well as artificial light sources. Count rates from such diffuse light are a background for EAS detections in future missions and relevant factor for the analysis of EAS events. We also obtain the geographical distribution of the count rates over a ∼780 km 2 area along the balloon trajectory. In developed areas, light sources such as the airport, mines, and factories are clearly identified. This demonstrates the correct location of signals that will be required for the EAS analysis in future missions. Although a precise determination of count rates is relevant for the existing instruments, the absolute intensity of diffuse light is deduced for the limited conditions by assuming spectra models and considering simulations of the instrument response. Based on the study of diffuse light by EUSO-Balloon, we also discuss the implications for coming pathfinders and future space-based UHECR observation missions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Airglow; EUSO-Balloon; Extensive air shower; JEM-EUSO; Ultra-high energy cosmic ray

XIPE: The X-ray imaging polarimetry explorer - Soffitta, P.; Bellazzini, R.; Bozzo, E.; Burwitz, V.; Castro-Tirado, A. J.; Costa, E.; Courvoisier, T.; Feng, H.; Gburek, S.; Goosmann, R.; Karas, V.; Matt, G.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
XIPE, the X-ray Imaging Polarimetry Explorer, is a mission dedicated to X-ray Astronomy. At the time of writing XIPE is in a competitive phase A as fourth medium size mission of ESA (M4). It promises to reopen the polarimetry window in high energy Astrophysics after more than 4 decades thanks to a detector that efficiently exploits the photoelectric effect and to X-ray optics with large effective area. XIPE uniqueness is time-spectrally-spatially-resolved X-ray polarimetry as a breakthrough in high energy astrophysics and fundamental physics. Indeed the payload consists of three Gas Pixel Detectors at the focus of three X-ray optics with a total effective area larger than one XMM mirror but with a low weight. The payload is compatible with the fairing of the Vega launcher. XIPE is designed as an observatory for X-ray astronomers with 75 % of the time dedicated to a Guest Observer competitive program and it is organized as a consortium across Europe with main contributions from Italy, Germany, Spain, United Kingdom, Poland, Sweden.
Keywords: Gas Pixel Detector; Polarimetry; X-ray Astronomy; X-ray optics

X-ray detection of a nova in the fireball phase - König, Ole; Wilms, Jörn; Arcodia, Riccardo; Dauser, Thomas; Dennerl, Konrad; Doroshenko, Victor; Haberl, Frank; Hämmerich, Steven; Kirsch, Christian; Kreykenbohm, Ingo; Lorenz, Maximilian; Malyali, Adam; et al. (Nature, 2022)
Novae are caused by runaway thermonuclear burning in the hydrogen-rich envelopes of accreting white dwarfs, which leads to a rapid expansion of the envelope and the ejection of most of its mass1,2. Theory has predicted the existence of a ‘fireball’ phase following directly on from the runaway fusion, which should be observable as a short, bright and soft X-ray flash before the nova becomes visible in the optical3–5. Here we report observations of a bright and soft X-ray flash associated with the classical Galactic nova YZ Reticuli 11 h before its 9 mag optical brightening. No X-ray source was detected 4 h before and after the event, constraining the duration of the flash to shorter than 8 h. In agreement with theoretical predictions4,6–8, the source’s spectral shape is consistent with a black-body of 3.27+0.11−0.33 × 105 K (28.2+0.9−2.8 eV), or a white dwarf atmosphere, radiating at the Eddington luminosity, with a photosphere that is only slightly larger than a typical white dwarf.
CRIS-Team Scopus Importer:2022-06-03

X-Ray emission from SN1885A - Prucker, Marie; Sasaki, Manami; Schlegel, E.; Knies, Jonathan; Weber, Philipp; Kreykenbohm, Ingo; Wilms, Jörn (Astronomy & Astrophysics, 2025)
The historical supernova (SN) S Andromedae (S And or SN1885A) in the Andromeda Galaxy (M31) was discovered in August 1885 and since then has been studied extensively in multi-wavelength observations. Although the remnant of S And could be detected in optical images, so far no X-ray source has been reported at the position of S And. In this work we report the first detection of X-ray emission from the remnant of SN1885A with a significance of Ï = 3.43 using Chandra High-Resolution Camera (HRC) data taken in the imaging (I) mode. A total of 45 Chandra HRC-I observations were analysed, which corresponds to 940 ks of exposure time. A faint X-ray source could be detected at the reported position of the supernova remnant (SNR) 1885 and the corresponding X-ray luminosity in the 0.1 10 keV band was obtained. The resulting value from merging all 45 observations amounts to L0.110keV = (63+4) A- 1033 erg s1. To contextualise the results, the luminosity was compared to the X-ray luminosities of four of the oldest known X-ray SNe, some younger Galactic remnants, some SNRs in M31, and to theoretical predictions. The X-ray luminosity of SNR1885 is three to four orders of magnitude lower compared to the other examined remnants. A comparison to theoretical models shows that such low X-ray luminosities can only be produced if the ejecta is still expanding freely into a low-density interstellar medium (ISM). On the other hand, strong absorption by a high-density medium surrounding the freely expanding ejecta could also account for the lack of X-ray emission. Furthermore, the extremely low emission in X-rays could be an indication that the X-ray luminosity decreases faster towards the end of the ejecta-dominated (ED) phase in the evolution of SNRs than in the beginning.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Galaxies: individual: M31; ISM: supernova remnants; X-rays: individuals: S And; X-rays: individuals: SN1885A

X-ray spectral and flux variability of the microquasar GRS 1758-258 on timescales from weeks to years - Hirsch, Maria; Pottschmidt, Katja; Smith, David M.; Bodaghee, Arash; Cadolle Bel, Marion; Grinberg, Victoria; Hell, Natalie; Krauß, Felicia; Kreykenbohm, Ingo; Lohfink, Anne; Nowak, Michael A.; Rodrigues, Bárbara H.; et al. (Astronomy & Astrophysics, 2020)
We present the spectral and timing evolution of the persistent black hole X-ray binary GRS 1758-258 based on almost 12 years of observations using the Rossi X-ray Timing Explorer Proportional Counter Array. While the source was predominantly found in the hard state during this time, it entered the thermally dominated soft state seven times. In the soft state GRS 1758-258 shows a strong decline in flux above 3 keV rather than the pivoting flux around 10 keV more commonly shown by black hole transients. In its 3-20 keV hardness intensity diagram, GRS 1758-258 shows a hysteresis of hard and soft state fluxes typical for transient sources in outburst. The RXTE-PCA and RXTE-ASM long-term light curves do not show any orbital modulations in the range of 2-30 d. However, in the dynamic power spectra significant peaks drift between 18.47 and 18.04 d for the PCA data, while less significant signatures between 19 d and 20 d are seen for the ASM data as well as for the Swift/BAT data. We discuss different models for the hysteresis behavior during state transitions as well as possibilities for the origin of the long term variation in the context of a warped accretion disk.
CRIS-Team Scopus Importer:2020-05-02
Keywords: X-rays: binaries; X-rays: individuals: GRS 1758-258

X-ray variation statistics and wind clumping in Vela X-1 - Fürst, Felix; Kreykenbohm, Ingo; Pottschmidt, K.; Wilms, Jörn; Hanke, Manfred; Rothschild, R. E.; Kretschmar, Peter; Schulz, N. S.; Huenemoerder, D. P.; Klochkov, D.; Staubert, R. (Astronomy & Astrophysics, 2010)
We investigate the structure of the wind in the neutron star X-ray binary system Vela X-1 by analyzing its flaring behavior. Vela X-1 shows constant flaring, with some flares reaching fluxes of more than 3.0 Crab between 20-60 keV for several 100 s, while the average flux is around 250 mCrab. We analyzed all archival INTEGRAL data, calculating the brightness distribution in the 20-60 keV band, which, as we show, closely follows a log-normal distribution. Orbital resolved analysis shows that the structure is strongly variable, explainable by shocks and a fluctuating accretion wake. Analysis of RXTE ASM data suggests a strong orbital change of N(H). Accreted clump masses derived from the INTEGRAL data are on the order of 5x10(19) - 10(21) g. We show that the lightcurve can be described with a model of multiplicative random numbers. In the course of the simulation we calculate the power spectral density of the system in the 20-100 keV energy band and show that it follows a red-noise power law. We suggest that a mixture of a clumpy wind, shocks, and turbulence can explain the measured mass distribution. As the recently discovered class of supergiant fast X-ray transients (SFXT) seems to show the same parameters for the wind, the link between persistent HMXB like Vela X-1 and SFXT is further strengthened.
Keywords: accretion; accretion disks; X-rays: binaries; X-rays: individuals: Vela X-1; methods: statistical